Risk-aware stochastic shortest path - Meggendorfer, Tobias (Proceedings of the 36th AAAI Conference on Artificial Intelligence, AAAI 2022)
We treat the problem of risk-aware control for stochastic shortest path (SSP) on Markov decision processes (MDP). Typically, expectation is considered for SSP, which however is oblivious to the incurred risk. We present an alternative view, instead optimizing conditional value-at-risk (CVaR), an established risk measure. We treat both Markov chains as well as MDP and introduce, through novel insights, two algorithms, based on linear programming and value iteration, respectively. Both algorithms offer precise and provably correct solutions. Evaluation of our prototype implementation shows that risk-aware control is feasible on several moderately sized models.

Cross-client Label Propagation for transductive federated learning - Scott, Jonathan A; Yeo, Michelle X; Lampert, Christoph (arXiv)
We present Cross-Client Label Propagation(XCLP), a new method for transductive federated learning. XCLP estimates a data graph jointly from the data of multiple clients and computes labels for the unlabeled data by propagating label information across the graph. To avoid clients having to share their data with anyone, XCLP employs two cryptographically secure protocols: secure Hamming distance computation and secure summation. We demonstrate two distinct applications of XCLP within federated learning. In the first, we use it in a one-shot way to predict labels for unseen test points. In the second, we use it to repeatedly pseudo-label unlabeled training data in a federated semi-supervised setting. Experiments on both real federated and standard benchmark datasets show that in both applications XCLP achieves higher classification accuracy than alternative approaches.

Generalization in Multi-objective machine learning - Súkeník, Peter; Lampert, Christoph (arXiv)
Modern machine learning tasks often require considering not just one but multiple objectives. For example, besides the prediction quality, this could be the efficiency, robustness or fairness of the learned models, or any of their combinations. Multi-objective learning offers a natural framework for handling such problems without having to commit to early trade-offs. Surprisingly, statistical learning theory so far offers almost no insight into the generalization properties of multi-objective learning. In this work, we make first steps to fill this gap: we establish foundational generalization bounds for the multi-objective setting as well as generalization and excess bounds for learning with scalarizations. We also provide the first theoretical analysis of the relation between the Pareto-optimal sets of the true objectives and the Pareto-optimal sets of their empirical approximations from training data. In particular, we show a surprising asymmetry: all Pareto-optimal solutions can be approximated by empirically Pareto-optimal ones, but not vice versa.

FLEA: Provably robust fair multisource learning from unreliable training data - Iofinova, Eugenia B; Konstantinov, Nikola H; Lampert, Christoph (Transactions on Machine Learning Research)
Fairness-aware learning aims at constructing classifiers that not only make accurate predictions, but also do not discriminate against specific groups. It is a fast-growing area of machine learning with far-reaching societal impact. However, existing fair learning methods are vulnerable to accidental or malicious artifacts in the training data, which can cause them to unknowingly produce unfair classifiers. In this work we address the problem of fair learning from unreliable training data in the robust multisource setting, where the available training data comes from multiple sources, a fraction of which might not be representative of the true data distribution. We introduce FLEA, a filtering-based algorithm that identifies and suppresses those data sources that would have a negative impact on fairness or accuracy if they were used for training. As such, FLEA is not a replacement of prior fairness-aware learning methods but rather an augmentation that makes any of them robust against unreliable training data. We show the effectiveness of our approach by a diverse range of experiments on multiple datasets. Additionally, we prove formally that –given enough data– FLEA protects the learner against corruptions as long as the fraction of affected data sources is less than half. Our source code and documentation are available at https://github.com/ISTAustria-CVML/FLEA.

On compatible matchings - Aichholzer, Oswin; Arroyo Guevara, Alan M; Masárová, Zuzana; Parada, Irene; Perz, Daniel; Pilz, Alexander; Tkadlec, Josef; Vogtenhuber, Birgit (Journal of Graph Algorithms and Applications)
A matching is compatible to two or more labeled point sets of size n with labels {1, . . . , n} if its straight-line drawing on each of these point sets is crossing-free. We study the maximum number of edges in a matching compatible to two or more labeled point sets in general position in the plane. We show that for any two labeled sets of n points in convex position there exists a compatible matching with ⌊√2n + 1 − 1⌋ edges. More generally, for any ℓ labeled point sets we construct compatible matchings of size Ω(n1/ℓ). As a corresponding upper bound, we use probabilistic arguments to show that for any ℓ given sets of n points there exists a labeling of each set such that the largest compatible matching has O(n2/(ℓ+1)) edges. Finally, we show that Θ(log n) copies of any set of n points are necessary and sufficient for the existence of labelings of these point sets such that any compatible matching consists only of a single edge.

Open problems on billiards and geometric optics - Bialy, Misha; Fiorebe, Corentin; Glutsyuk, Alexey; Levi, Mark; Plakhov, Alexander; Tabachnikov, Serge (Arnold Mathematical Journal)
This is a collection of problems composed by some participants of the workshop “Differential Geometry, Billiards, and Geometric Optics” that took place at CIRM on October 4–8, 2021.

Repeated prophet inequality with near-optimal bounds - Chatterjee, Krishnendu; Mohammadi, Mona; Saona Urmeneta, Raimundo J (arXiv)
In modern sample-driven Prophet Inequality, an adversary chooses a sequence of n items with values v1,v2,…,vn to be presented to a decision maker (DM). The process follows in two phases. In the first phase (sampling phase), some items, possibly selected at random, are revealed to the DM, but she can never accept them. In the second phase, the DM is presented with the other items in a random order and online fashion. For each item, she must make an irrevocable decision to either accept the item and stop the process or reject the item forever and proceed to the next item. The goal of the DM is to maximize the expected value as compared to a Prophet (or offline algorithm) that has access to all information. In this setting, the sampling phase has no cost and is not part of the optimization process. However, in many scenarios, the samples are obtained as part of the decision-making process. We model this aspect as a two-phase Prophet Inequality where an adversary chooses a sequence of 2n items with values v1,v2,…,v2n and the items are randomly ordered. Finally, there are two phases of the Prophet Inequality problem with the first n-items and the rest of the items, respectively. We show that some basic algorithms achieve a ratio of at most 0.450. We present an algorithm that achieves a ratio of at least 0.495. Finally, we show that for every algorithm the ratio it can achieve is at most 0.502. Hence our algorithm is near-optimal.

CGX: Adaptive system support for communication-efficient deep learning - Markov, Ilia; Ramezanikebrya, Hamidreza; Alistarh, Dan-Adrian (Proceedings of the 23rd ACM/IFIP International Middleware Conference)
The ability to scale out training workloads has been one of the key performance enablers of deep learning. The main scaling approach is data-parallel GPU-based training, which has been boosted by hardware and software support for highly efficient point-to-point communication, and in particular via hardware bandwidth over-provisioning. Overprovisioning comes at a cost: there is an order of magnitude price difference between "cloud-grade" servers with such support, relative to their popular "consumer-grade" counterparts, although single server-grade and consumer-grade GPUs can have similar computational envelopes. In this paper, we show that the costly hardware overprovisioning approach can be supplanted via algorithmic and system design, and propose a framework called CGX, which provides efficient software support for compressed communication in ML applications, for both multi-GPU single-node training, as well as larger-scale multi-node training. CGX is based on two technical advances: At the system level, it relies on a re-developed communication stack for ML frameworks, which provides flexible, highly-efficient support for compressed communication. At the application level, it provides seamless, parameter-free integration with popular frameworks, so that end-users do not have to modify training recipes, nor significant training code. This is complemented by a layer-wise adaptive compression technique which dynamically balances compression gains with accuracy preservation. CGX integrates with popular ML frameworks, providing up to 3X speedups for multi-GPU nodes based on commodity hardware, and order-of-magnitude improvements in the multi-node setting, with negligible impact on accuracy.

Towards differential relational privacy and its use in question answering - Bombari, Simone; Achille, Alessandro; Wang, Zijian; Wang, Yu-Xiang; Xie, Yusheng; Singh, Kunwar Yashraj; Appalaraju, Srikar; Mahadevan, Vijay; Soatto, Stefano (arXiv)
Memorization of the relation between entities in a dataset can lead to privacy issues when using a trained model for question answering. We introduce Relational Memorization (RM) to understand, quantify and control this phenomenon. While bounding general memorization can have detrimental effects on the performance of a trained model, bounding RM does not prevent effective learning. The difference is most pronounced when the data distribution is long-tailed, with many queries having only few training examples: Impeding general memorization prevents effective learning, while impeding only relational memorization still allows learning general properties of the underlying concepts. We formalize the notion of Relational Privacy (RP) and, inspired by Differential Privacy (DP), we provide a possible definition of Differential Relational Privacy (DrP). These notions can be used to describe and compute bounds on the amount of RM in a trained model. We illustrate Relational Privacy concepts in experiments with large-scale models for Question Answering.

Integral points of bounded height on a certain toric variety - Wilsch, Florian Alexander (arXiv)
We determine an asymptotic formula for the number of integral points of bounded height on a certain toric variety, which is incompatible with part of a preprint by Chambert-Loir and Tschinkel. We provide an alternative interpretation of the asymptotic formula we get. To do so, we construct an analogue of Peyre's constant $α$ and describe its relation to a new obstruction to the Zariski density of integral points in certain regions of varieties.
Keywords: Integral point; toric variety; Manin's conjecture

Almost-orthogonal layers for efficient general-purpose Lipschitz networks - Prach, Bernd; Lampert, Christoph (Computer Vision – ECCV 2022)
It is a highly desirable property for deep networks to be robust against small input changes. One popular way to achieve this property is by designing networks with a small Lipschitz constant. In this work, we propose a new technique for constructing such Lipschitz networks that has a number of desirable properties: it can be applied to any linear network layer (fully-connected or convolutional), it provides formal guarantees on the Lipschitz constant, it is easy to implement and efficient to run, and it can be combined with any training objective and optimization method. In fact, our technique is the first one in the literature that achieves all of these properties simultaneously. Our main contribution is a rescaling-based weight matrix parametrization that guarantees each network layer to have a Lipschitz constant of at most 1 and results in the learned weight matrices to be close to orthogonal. Hence we call such layers almost-orthogonal Lipschitz (AOL). Experiments and ablation studies in the context of image classification with certified robust accuracy confirm that AOL layers achieve results that are on par with most existing methods. Yet, they are simpler to implement and more broadly applicable, because they do not require computationally expensive matrix orthogonalization or inversion steps as part of the network architecture. We provide code at https://github.com/berndprach/AOL.

Histone H2B.8 compacts flowering plant sperm through chromatin phase separation - Buttress, Toby; He, Shengbo; Wang, Liang; Zhou, Shaoli; Saalbach, Gerhard; Vickers, Martin; Li, Guohong; Li, Pilong; Feng, Xiaoqi (Nature)
Sperm chromatin is typically transformed by protamines into a compact and transcriptionally inactive state1,2. Sperm cells of flowering plants lack protamines, yet they have small, transcriptionally active nuclei with chromatin condensed through an unknown mechanism3,4. Here we show that a histone variant, H2B.8, mediates sperm chromatin and nuclear condensation in Arabidopsis thaliana. Loss of H2B.8 causes enlarged sperm nuclei with dispersed chromatin, whereas ectopic expression in somatic cells produces smaller nuclei with aggregated chromatin. This result demonstrates that H2B.8 is sufficient for chromatin condensation. H2B.8 aggregates transcriptionally inactive AT-rich chromatin into phase-separated condensates, which facilitates nuclear compaction without reducing transcription. Reciprocal crosses show that mutation of h2b.8 reduces male transmission, which suggests that H2B.8-mediated sperm compaction is important for fertility. Altogether, our results reveal a new mechanism of nuclear compaction through global aggregation of unexpressed chromatin. We propose that H2B.8 is an evolutionary innovation of flowering plants that achieves nuclear condensation compatible with active transcription.

DNA methylation dynamics during germline development - He, Shengbo; Feng, Xiaoqi (Journal of Integrative Plant Biology)
DNA methylation plays essential homeostatic functions in eukaryotic genomes. In animals, DNA methylation is also developmentally regulated and, in turn, regulates development. In the past two decades, huge research effort has endorsed the understanding that DNA methylation plays a similar role in plant development, especially during sexual reproduction. The power of whole-genome sequencing and cell isolation techniques, as well as bioinformatics tools, have enabled recent studies to reveal dynamic changes in DNA methylation during germline development. Furthermore, the combination of these technological advances with genetics, developmental biology and cell biology tools has revealed functional methylation reprogramming events that control gene and transposon activities in flowering plant germlines. In this review, we discuss the major advances in our knowledge of DNA methylation dynamics during male and female germline development in flowering plants.
Keywords: Plant Science; General Biochemistry; Genetics and Molecular Biology; Biochemistry

Tissue-wide genetic and cellular landscape shapes the execution of sequential PRC2 functions in neural stem cell lineage progression - Amberg, Nicole; Pauler, Florian; Streicher, Carmen; Hippenmeyer, Simon (Science Advances)
The generation of a correctly-sized cerebral cortex with all-embracing neuronal and glial cell-type diversity critically depends on faithful radial glial progenitor (RGP) cell proliferation/differentiation programs. Temporal RGP lineage progression is regulated by Polycomb Repressive Complex 2 (PRC2) and loss of PRC2 activity results in severe neurogenesis defects and microcephaly. How PRC2-dependent gene expression instructs RGP lineage progression is unknown. Here we utilize Mosaic Analysis with Double Markers (MADM)-based single cell technology and demonstrate that PRC2 is not cell-autonomously required in neurogenic RGPs but rather acts at the global tissue-wide level. Conversely, cortical astrocyte production and maturation is cell-autonomously controlled by PRC2-dependent transcriptional regulation. We thus reveal highly distinct and sequential PRC2 functions in RGP lineage progression that are dependent on complex interplays between intrinsic and tissue-wide properties. In a broader context our results imply a critical role for the genetic and cellular niche environment in neural stem cell behavior.

Closed-loop control of direct ink writing via reinforcement learning - Piovarci, Michael; Foshey, Michael; Xu, Jie; Erps, Timothy; Babaei, Vahid; Didyk, Piotr; Rusinkiewicz, Szymon; Matusik, Wojciech; Bickel, Bernd (ACM Transactions on Graphics)
Enabling additive manufacturing to employ a wide range of novel, functional materials can be a major boost to this technology. However, making such materials printable requires painstaking trial-and-error by an expert operator, as they typically tend to exhibit peculiar rheological or hysteresis properties. Even in the case of successfully finding the process parameters, there is no guarantee of print-to-print consistency due to material differences between batches. These challenges make closed-loop feedback an attractive option where the process parameters are adjusted on-the-fly. There are several challenges for designing an efficient controller: the deposition parameters are complex and highly coupled, artifacts occur after long time horizons, simulating the deposition is computationally costly, and learning on hardware is intractable. In this work, we demonstrate the feasibility of learning a closed-loop control policy for additive manufacturing using reinforcement learning. We show that approximate, but efficient, numerical simulation is sufficient as long as it allows learning the behavioral patterns of deposition that translate to real-world experiences. In combination with reinforcement learning, our model can be used to discover control policies that outperform baseline controllers. Furthermore, the recovered policies have a minimal sim-to-real gap. We showcase this by applying our control policy in-vivo on a single-layer, direct ink writing printer.

Near-optimal leader election in population protocols on graphs - Alistarh, Dan-Adrian; Rybicki, Joel; Voitovych, Sasha (Proceedings of the Annual ACM Symposium on Principles of Distributed Computing)
In the stochastic population protocol model, we are given a connected graph with n nodes, and in every time step, a scheduler samples an edge of the graph uniformly at random and the nodes connected by this edge interact. A fundamental task in this model is stable leader election, in which all nodes start in an identical state and the aim is to reach a configuration in which (1) exactly one node is elected as leader and (2) this node remains as the unique leader no matter what sequence of interactions follows. On cliques, the complexity of this problem has recently been settled: time-optimal protocols stabilize in Θ(n log n) expected steps using Θ(log log n) states, whereas protocols that use O(1) states require Θ(n2) expected steps. In this work, we investigate the complexity of stable leader election on general graphs. We provide the first non-trivial time lower bounds for leader election on general graphs, showing that, when moving beyond cliques, the complexity landscape of leader election becomes very diverse: the time required to elect a leader can range from O(1) to Θ(n3) expected steps. On the upper bound side, we first observe that there exists a protocol that is time-optimal on many graph families, but uses polynomially-many states. In contrast, we give a near-time-optimal protocol that uses only O(log2n) states that is at most a factor log n slower. Finally, we show that the constant-state protocol of Beauquier et al. [OPODIS 2013] is at most a factor n log n slower than the fast polynomial-state protocol. Moreover, among constant-state protocols, this protocol has near-optimal average case complexity on dense random graphs.

High-dimensional expansion and crossing numbers of simplicial complexes - Wild, Pascal
In this dissertation we study coboundary expansion of simplicial complex with a view of giving geometric applications. Our main novel tool is an equivariant version of Gromov's celebrated Topological Overlap Theorem. The equivariant topological overlap theorem leads to various geometric applications including a quantitative non-embeddability result for sufficiently thick buildings (which partially resolves a conjecture of Tancer and Vorwerk) and an improved lower bound on the pair-crossing number of (bounded degree) expander graphs. Additionally, we will give new proofs for several known lower bounds for geometric problems such as the number of Tverberg partitions or the crossing number of complete bipartite graphs. For the aforementioned applications one is naturally lead to study expansion properties of joins of simplicial complexes. In the presence of a special certificate for expansion (as it is the case, e.g., for spherical buildings), the join of two expanders is an expander. On the flip-side, we report quite some evidence that coboundary expansion exhibits very non-product-like behaviour under taking joins. For instance, we exhibit infinite families of graphs $(G_n)_{n\in \mathbb{N}}$ and $(H_n)_{n\in\mathbb{N}}$ whose join $G_n*H_n$ has expansion of lower order than the product of the expansion constant of the graphs. Moreover, we show an upper bound of $(d+1)/2^d$ on the normalized coboundary expansion constants for the complete multipartite complex $[n]^{*(d+1)}$ (under a mild divisibility condition on $n$). Via the probabilistic method the latter result extends to an upper bound of $(d+1)/2^d+ε$ on the coboundary expansion constant of the spherical building associated with $PGL_{d+2}(\mathbb{F}_q)$ for any $ε>0$ and sufficiently large $q=q(ε)$. This disproves a conjecture of Lubotzky, Meshulam and Mozes -- in a rather strong sense. By improving on existing lower bounds we make further progress towards closing the gap between the known lower and upper bounds on the coboundary expansion constants of $[n]^{*(d+1)}$. The best improvements we achieve using computer-aided proofs and flag algebras. The exact value even for the complete $3$-partite $2$-dimensional complex $[n]^{*3}$ remains unknown but we are happy to conjecture a precise value for every $n$. %Moreover, we show that a previously shown lower bound on the expansion constant of the spherical building associated with $PGL_{2}(\mathbb{F}_q)$ is not tight. In a loosely structured, last chapter of this thesis we collect further smaller observations related to expansion. We point out a link between discrete Morse theory and a technique for showing coboundary expansion, elaborate a bit on the hardness of computing coboundary expansion constants, propose a new criterion for coboundary expansion (in a very dense setting) and give one way of making the folklore result that expansion of links is a necessary condition for a simplicial complex to be an expander precise.

Genetic basis of flower colour as a model for adaptive evolution - Matejovicova, Lenka
Although we often see studies focusing on simple or even discrete traits in studies of colouration, the variation of “appearance” phenotypes found in nature is often more complex, continuous and high-dimensional. Therefore, we developed automated methods suitable for large datasets of genomes and images, striving to account for their complex nature, while minimising human bias. We used these methods on a dataset of more than 20, 000 plant SNP genomes and corresponding fower images from a hybrid zone of two subspecies of Antirrhinum majus with distinctly coloured fowers to improve our understanding of the genetic nature of the fower colour in our study system. Firstly, we use the advantage of large numbers of genotyped plants to estimate the haplotypes in the main fower colour regulating region. We study colour- and geography-related characteristics of the estimated haplotypes and how they connect to their relatedness. We show discrepancies from the expected fower colour distributions given the genotype and identify particular haplotypes leading to unexpected phenotypes. We also confrm a signifcant defcit of the double recessive recombinant and quite surprisingly, we show that haplotypes of the most frequent parental type are much less variable than others. Secondly, we introduce our pipeline capable of processing tens of thousands of full fower images without human interaction and summarising each image into a set of informative scores. We show the compatibility of these machine-measured fower colour scores with the previously used manual scores and study impact of external efect on the resulting scores. Finally, we use the machine-measured fower colour scores to ft and examine a phenotype cline across the hybrid zone in Planoles using full fower images as opposed to discrete, manual scores and compare it with the genotypic cline.

Predictive learning enables neural networks to learn complex working memory tasks - Van Der Plas, Thijs L.; Vogels, Tim P; Manohar, Sanjay G. (Proceedings of Machine Learning Research)
Brains are thought to engage in predictive learning - learning to predict upcoming stimuli - to construct an internal model of their environment. This is especially notable for spatial navigation, as first described by Tolman’s latent learning tasks. However, predictive learning has also been observed in sensory cortex, in settings unrelated to spatial navigation. Apart from normative frameworks such as active inference or efficient coding, what could be the utility of learning to predict the patterns of occurrence of correlated stimuli? Here we show that prediction, and thereby the construction of an internal model of sequential stimuli, can bootstrap the learning process of a working memory task in a recurrent neural network. We implemented predictive learning alongside working memory match-tasks, and networks emerged to solve the prediction task first by encoding information across time to predict upcoming stimuli, and then eavesdropped on this solution to solve the matching task. Eavesdropping was most beneficial when neural resources were limited. Hence, predictive learning acts as a general neural mechanism to learn to store sensory information that can later be essential for working memory tasks.

Revisiting the adversarial robustness-accuracy tradeoff in robot learning - Lechner, Mathias; Amini, Alexander; Rus, Daniela; Henzinger, Thomas A (arXiv)
Adversarial training (i.e., training on adversarially perturbed input data) is a well-studied method for making neural networks robust to potential adversarial attacks during inference. However, the improved robustness does not come for free but rather is accompanied by a decrease in overall model accuracy and performance. Recent work has shown that, in practical robot learning applications, the effects of adversarial training do not pose a fair trade-off but inflict a net loss when measured in holistic robot performance. This work revisits the robustness-accuracy trade-off in robot learning by systematically analyzing if recent advances in robust training methods and theory in conjunction with adversarial robot learning can make adversarial training suitable for real-world robot applications. We evaluate a wide variety of robot learning tasks ranging from autonomous driving in a high-fidelity environment amenable to sim-to-real deployment, to mobile robot gesture recognition. Our results demonstrate that, while these techniques make incremental improvements on the trade-off on a relative scale, the negative side-effects caused by adversarial training still outweigh the improvements by an order of magnitude. We conclude that more substantial advances in robust learning methods are necessary before they can benefit robot learning tasks in practice.

Coupling 3D liquid simulation with 2D wave propagation for large scale water surface animation using the equivalent sources method - Schreck, Camille; Wojtan, Christopher J (Computer Graphics Forum)
This paper proposes a method for simulating liquids in large bodies of water by coupling together a water surface wave simulator with a 3D Navier-Stokes simulator. The surface wave simulation uses the equivalent sources method (ESM) to efficiently animate large bodies of water with precisely controllable wave propagation behavior. The 3D liquid simulator animates complex non-linear fluid behaviors like splashes and breaking waves using off-the-shelf simulators using FLIP or the level set method with semi-Lagrangian advection. We combine the two approaches by using the 3D solver to animate localized non-linear behaviors, and the 2D wave solver to animate larger regions with linear surface physics. We use the surface motion from the 3D solver as boundary conditions for 2D surface wave simulator, and we use the velocity and surface heights from the 2D surface wave simulator as boundary conditions for the 3D fluid simulation. We also introduce a novel technique for removing visual artifacts caused by numerical errors in 3D fluid solvers: we use experimental data to estimate the artificial dispersion caused by the 3D solver and we then carefully tune the wave speeds of the 2D solver to match it, effectively eliminating any differences in wave behavior across the boundary. To the best of our knowledge, this is the first time such a empirically driven error compensation approach has been used to remove coupling errors from a physics simulator. Our coupled simulation approach leverages the strengths of each simulation technique, animating large environments with seamless transitions between 2D and 3D physics.

Even maps, the Colin de Verdière number and representations of graphs - Kaluza, Vojtech; Tancer, Martin (Combinatorica)
Van der Holst and Pendavingh introduced a graph parameter σ, which coincides with the more famous Colin de Verdière graph parameter μ for small values. However, the definition of a is much more geometric/topological directly reflecting embeddability properties of the graph. They proved μ(G) ≤ σ(G) + 2 and conjectured σ(G) ≤ σ(G) for any graph G. We confirm this conjecture. As far as we know, this is the first topological upper bound on σ(G) which is, in general, tight. Equality between μ and σ does not hold in general as van der Holst and Pendavingh showed that there is a graph G with μ(G) ≤ 18 and σ(G) ≥ 20. We show that the gap appears at much smaller values, namely, we exhibit a graph H for which μ(H) ≥ 7 and σ(H) ≥ 8. We also prove that, in general, the gap can be large: The incidence graphs Hq of finite projective planes of order q satisfy μ(Hq) ∈ O(q3/2) and σ(Hq) ≥ q2.

Equidistribution and freeness on Grassmannians - Browning, Timothy D; Horesh, Tal; Wilsch, Florian Alexander (Algebra & Number Theory)
We associate a certain tensor product lattice to any primitive integer lattice and ask about its typical shape. These lattices are related to the tangent bundle of Grassmannians and their study is motivated by Peyre's programme on "freeness" for rational points of bounded height on Fano varieties.

Multitier mechanics control stromal adaptations in swelling lymph nodes - Assen, Frank P; Abe, Jun; Hons, Miroslav; Hauschild, Robert; Shamipour, Shayan; Kaufmann, Walter; Costanzo, Tommaso; Krens, Gabriel; Brown, Markus; Ludewig, Burkhard; Hippenmeyer, Simon; Heisenberg, Carl-Philipp J; et al. (Nature Immunology)
Lymph nodes (LNs) comprise two main structural elements: fibroblastic reticular cells that form dedicated niches for immune cell interaction and capsular fibroblasts that build a shell around the organ. Immunological challenge causes LNs to increase more than tenfold in size within a few days. Here, we characterized the biomechanics of LN swelling on the cellular and organ scale. We identified lymphocyte trapping by influx and proliferation as drivers of an outward pressure force, causing fibroblastic reticular cells of the T-zone (TRCs) and their associated conduits to stretch. After an initial phase of relaxation, TRCs sensed the resulting strain through cell matrix adhesions, which coordinated local growth and remodeling of the stromal network. While the expanded TRC network readopted its typical configuration, a massive fibrotic reaction of the organ capsule set in and countered further organ expansion. Thus, different fibroblast populations mechanically control LN swelling in a multitier fashion.

The topological correctness of PL approximations of isomanifolds - Boissonnat, Jean-Daniel; Wintraecken, Mathijs (Foundations of Computational Mathematics)
Isomanifolds are the generalization of isosurfaces to arbitrary dimension and codimension, i.e. manifolds defined as the zero set of some multivariate vector-valued smooth function f : Rd → Rd−n. A natural (and efficient) way to approximate an isomanifold is to consider its Piecewise-Linear (PL) approximation based on a triangulation T of the ambient space Rd. In this paper, we give conditions under which the PL-approximation of an isomanifold is topologically equivalent to the isomanifold. The conditions are easy to satisfy in the sense that they can always be met by taking a sufficiently fine triangulation T . This contrasts with previous results on the triangulation of manifolds where, in arbitrary dimensions, delicate perturbations are needed to guarantee topological correctness, which leads to strong limitations in practice. We further give a bound on the Fréchet distance between the original isomanifold and its PL-approximation. Finally we show analogous results for the PL-approximation of an isomanifold with boundary.

On the size of the maximum of incomplete Kloosterman sums - Bonolis, Dante (Mathematical Proceedings of the Cambridge Philosophical Society)
Let t : Fp → C be a complex valued function on Fp. A classical problem in analytic number theory is bounding the maximum M(t) := max 0≤H<p ∣ 1/√p ∑ 0≤n<H t (n) ∣ of the absolute value of the incomplete sums(1/√p)∑0≤n<H t (n). In this very general context one of the most important results is the Pólya–Vinogradov bound M(t)≤IIˆtII∞ log 3p, where ˆt : Fp → C is the normalized Fourier transform of t. In this paper we provide a lower bound for certain incomplete Kloosterman sums, namely we prove that for any ε > 0 there exists a large subset of a ∈ F×p such that for kl a,1,p : x → e((ax+x) / p) we have M(kla,1,p) ≥ (1−ε/√2π + o(1)) log log p, as p→∞. Finally, we prove a result on the growth of the moments of {M (kla,1,p)}a∈F×p. 2020 Mathematics Subject Classification: 11L03, 11T23 (Primary); 14F20, 60F10 (Secondary).

Resurgence analysis of quantum invariants of Seifert fibered homology spheres - Mistegaard, William; Andersen, Jørgen Ellegaard (Journal of the London Mathematical Society)
For a Seifert fibered homology sphere X we show that the q-series invariant Zˆ0(X; q) introduced by Gukov-Pei-Putrov-Vafa, is a resummation of the Ohtsuki series Z0(X). We show that for every even k ∈ N there exists a full asymptotic expansion of Zˆ0(X; q) for q tending to e 2πi/k, and in particular that the limit Zˆ0(X; e 2πi/k) exists and is equal to the WRT quantum invariant τk(X). We show that the poles of the Borel transform of Z0(X) coincide with the classical complex Chern-Simons values, which we further show classifies the corresponding components of the moduli space of flat SL(2, C)-connections.

Fourteen stations of auxin - Friml, Jiří (Cold Spring Harbor Perspectives in Biology)
Auxin has always been at the forefront of research in plant physiology and development. Since the earliest contemplations by Julius von Sachs and Charles Darwin, more than a century-long struggle has been waged to understand its function. This largely reflects the failures, successes, and inevitable progress in the entire field of plant signaling and development. Here I present 14 stations on our long and sometimes mystical journey to understand auxin. These highlights were selected to give a flavor of the field and to show the scope and limits of our current knowledge. A special focus is put on features that make auxin unique among phytohormones, such as its dynamic, directional transport network, which integrates external and internal signals, including self-organizing feedback. Accented are persistent mysteries and controversies. The unexpected discoveries related to rapid auxin responses and growth regulation recently disturbed our contentment regarding understanding of the auxin signaling mechanism. These new revelations, along with advances in technology, usher us into a new, exciting era in auxin research.

The assembly, regulation and function of the mitochondrial respiratory chain - Vercellino, Irene; Sazanov, Leonid A (Nature Reviews Molecular Cell Biology)
The mitochondrial oxidative phosphorylation system is central to cellular metabolism. It comprises five enzymatic complexes and two mobile electron carriers that work in a mitochondrial respiratory chain. By coupling the oxidation of reducing equivalents coming into mitochondria to the generation and subsequent dissipation of a proton gradient across the inner mitochondrial membrane, this electron transport chain drives the production of ATP, which is then used as a primary energy carrier in virtually all cellular processes. Minimal perturbations of the respiratory chain activity are linked to diseases; therefore, it is necessary to understand how these complexes are assembled and regulated and how they function. In this Review, we outline the latest assembly models for each individual complex, and we also highlight the recent discoveries indicating that the formation of larger assemblies, known as respiratory supercomplexes, originates from the association of the intermediates of individual complexes. We then discuss how recent cryo-electron microscopy structures have been key to answering open questions on the function of the electron transport chain in mitochondrial respiration and how supercomplexes and other factors, including metabolites, can regulate the activity of the single complexes. When relevant, we discuss how these mechanisms contribute to physiology and outline their deregulation in human diseases.

Integral points on singular del Pezzo surfaces - Derenthal, Ulrich; Wilsch, Florian Alexander (Journal of the Institute of Mathematics of Jussieu)
In order to study integral points of bounded log-anticanonical height on weak del Pezzo surfaces, we classify weak del Pezzo pairs. As a representative example, we consider a quartic del Pezzo surface of singularity type A1 + A3 and prove an analogue of Manin's conjecture for integral points with respect to its singularities and its lines.
Keywords: Integral points; del Pezzo surface; universal torsor; Manin’s conjecture

Disentangling cadherin-mediated cell-cell interactions in collective cancer cell migration - Zisis, Themistoklis; Brückner, David; Brandstätter, Tom; Siow, Wei Xiong; d’Alessandro, Joseph; Vollmar, Angelika M.; Broedersz, Chase P.; Zahler, Stefan (Biophysical Journal)
Cell dispersion from a confined area is fundamental in a number of biological processes, including cancer metastasis. To date, a quantitative understanding of the interplay of single cell motility, cell proliferation, and intercellular contacts remains elusive. In particular, the role of E- and N-Cadherin junctions, central components of intercellular contacts, is still controversial. Combining theoretical modeling with in vitro observations, we investigate the collective spreading behavior of colonies of human cancer cells (T24). The spreading of these colonies is driven by stochastic single-cell migration with frequent transient cell-cell contacts. We find that inhibition of E- and N-Cadherin junctions decreases colony spreading and average spreading velocities, without affecting the strength of correlations in spreading velocities of neighboring cells. Based on a biophysical simulation model for cell migration, we show that the behavioral changes upon disruption of these junctions can be explained by reduced repulsive excluded volume interactions between cells. This suggests that in cancer cell migration, cadherin-based intercellular contacts sharpen cell boundaries leading to repulsive rather than cohesive interactions between cells, thereby promoting efficient cell spreading during collective migration.
Keywords: Biophysics

Scaling limit of the homogenization commutator for Gaussian coefficient fields - Duerinckx, Mitia; Fischer, Julian L; Gloria, Antoine (Annals of applied probability)
Consider a linear elliptic partial differential equation in divergence form with a random coefficient field. The solution operator displays fluctuations around its expectation. The recently developed pathwise theory of fluctuations in stochastic homogenization reduces the characterization of these fluctuations to those of the so-called standard homogenization commutator. In this contribution, we investigate the scaling limit of this key quantity: starting from a Gaussian-like coefficient field with possibly strong correlations, we establish the convergence of the rescaled commutator to a fractional Gaussian field, depending on the decay of correlations of the coefficient field, and we investigate the (non)degeneracy of the limit. This extends to general dimension $d\ge1$ previous results so far limited to dimension $d=1$, and to the continuum setting with strong correlations recent results in the discrete iid case.

Generalized quasi-metric semilattices - Dikranjan, Dikran; Giordano Bruno, Anna; Künzi, Hans Peter; Zava, Nicolò; Toller, Daniele (Topology and its Applications)
Motivated by the recent introduction of the intrinsic semilattice entropy, we study generalized quasi-metric semilattices and their categories. We investigate the relationship between these objects and generalized semivaluations, extending Nakamura and Schellekens' approach. Finally, we use this correspondence to compare the intrinsic semilattice entropy and the semigroup entropy induced in particular situations, like sets, torsion abelian groups and vector spaces.

Transcriptional analysis in the Arabidopsis roots reveals new regulators that link rac-GR24 treatment with changes in flavonol accumulation, root hair elongation and lateral root density - Struk, Sylwia; Braem, Lukas; Matthys, Cedrick; Walton, Alan; Vangheluwe, Nick; Van Praet, Stan; Jiang, Lingxiang; Baster, Pawel; De Cuyper, Carolien; Boyer, Francois-Didier; Stes, Elisabeth; Beeckman, Tom; et al. (Plant & Cell Physiology)
The synthetic strigolactone (SL) analog, rac-GR24, has been instrumental in studying the role of SLs as well as karrikins because it activates the receptors DWARF14 (D14) and KARRIKIN INSENSITIVE 2 (KAI2) of their signaling pathways, respectively. Treatment with rac-GR24 modifies the root architecture at different levels, such as decreasing the lateral root density (LRD), while promoting root hair elongation or flavonol accumulation. Previously, we have shown that the flavonol biosynthesis is transcriptionally activated in the root by rac-GR24 treatment, but, thus far, the molecular players involved in that response have remained unknown. To get an in-depth insight into the changes that occur after the compound is perceived by the roots, we compared the root transcriptomes of the wild type and the more axillary growth2 (max2) mutant, affected in both SL and karrikin signaling pathways, with and without rac-GR24 treatment. Quantitative reverse transcription (qRT)-PCR, reporter line analysis and mutant phenotyping indicated that the flavonol response and the root hair elongation are controlled by the ELONGATED HYPOCOTYL 5 (HY5) and MYB12 transcription factors, but HY5, in contrast to MYB12, affects the LRD as well. Furthermore, we identified the transcription factors TARGET OF MONOPTEROS 5 (TMO5) and TMO5 LIKE1 as negative and the Mediator complex as positive regulators of the rac-GR24 effect on LRD. Altogether, hereby, we get closer toward understanding the molecular mechanisms that underlay the rac-GR24 responses in the root.
Keywords: flavonols; MAX2; rac-Gr24; RNA-seq; root development; transcriptional regulation

Sobolev-to-Lipschitz property on QCD- spaces and applications - Dello Schiavo, Lorenzo; Suzuki, Kohei (Mathematische Annalen)
We prove the Sobolev-to-Lipschitz property for metric measure spaces satisfying the quasi curvature-dimension condition recently introduced in Milman (Commun Pure Appl Math, to appear). We provide several applications to properties of the corresponding heat semigroup. In particular, under the additional assumption of infinitesimal Hilbertianity, we show the Varadhan short-time asymptotics for the heat semigroup with respect to the distance, and prove the irreducibility of the heat semigroup. These results apply in particular to large classes of (ideal) sub-Riemannian manifolds.
Keywords: quasi curvature-dimension condition; sub-riemannian geometry; Sobolev-to-Lipschitz property; Varadhan short-time asymptotics

Index appearance record with preorders - Kretinsky, Jan; Meggendorfer, Tobias; Waldmann, Clara; Weininger, Maximilian (Acta Informatica)
Transforming ω-automata into parity automata is traditionally done using appearance records. We present an efficient variant of this idea, tailored to Rabin automata, and several optimizations applicable to all appearance records. We compare the methods experimentally and show that our method produces significantly smaller automata than previous approaches.
Keywords: computer networks and communications; information systems; software

Adiabatic theorem in the thermodynamic limit: Systems with a uniform gap - Henheik, Sven Joscha; Teufel, Stefan (Journal of Mathematical Physics)
We show that recent results on adiabatic theory for interacting gapped many-body systems on finite lattices remain valid in the thermodynamic limit. More precisely, we prove a generalized super-adiabatic theorem for the automorphism group describing the infinite volume dynamics on the quasi-local algebra of observables. The key assumption is the existence of a sequence of gapped finite volume Hamiltonians, which generates the same infinite volume dynamics in the thermodynamic limit. Our adiabatic theorem also holds for certain perturbations of gapped ground states that close the spectral gap (so it is also an adiabatic theorem for resonances and, in this sense, “generalized”), and it provides an adiabatic approximation to all orders in the adiabatic parameter (a property often called “super-adiabatic”). In addition to the existing results for finite lattices, we also perform a resummation of the adiabatic expansion and allow for observables that are not strictly local. Finally, as an application, we prove the validity of linear and higher order response theory for our class of perturbations for infinite systems. While we consider the result and its proof as new and interesting in itself, we also lay the foundation for the proof of an adiabatic theorem for systems with a gap only in the bulk, which will be presented in a follow-up article.
Keywords: mathematical physics; statistical and nonlinear physics

Inkjet printing of epitaxially connected nanocrystal superlattices - Balazs, Daniel; Erkan, N. Deniz; Quien, Michelle; Hanrath, Tobias (Nano Research)
Access to a blossoming library of colloidal nanomaterials provides building blocks for complex assembled materials. The journey to bring these prospects to fruition stands to benefit from the application of advanced processing methods. Epitaxially connected nanocrystal (or quantum dot) superlattices present a captivating model system for mesocrystals with intriguing emergent properties. The conventional processing approach to creating these materials involves assembling and attaching the constituent nanocrystals at the interface between two immiscible fluids. Processing small liquid volumes of the colloidal nanocrystal solution involves several complexities arising from the concurrent spreading, evaporation, assembly, and attachment. The ability of inkjet printers to deliver small (typically picoliter) liquid volumes with precise positioning is attractive to advance fundamental insights into the processing science, and thereby potentially enable new routes to incorporate the epitaxially connected superlattices into technology platforms. In this study, we identified the processing window of opportunity, including nanocrystal ink formulation and printing approach to enable delivery of colloidal nanocrystals from an inkjet nozzle onto the surface of a sessile droplet of the immiscible subphase. We demonstrate how inkjet printing can be scaled-down to enable the fabrication of epitaxially connected superlattices on patterned sub-millimeter droplets. We anticipate that insights from this work will spur on future advances to enable more mechanistic insights into the assembly processes and new avenues to create high-fidelity superlattices.
Keywords: interfacial assembly; colloidal nanocrystal; superlattice; inkjet printing

Global existence analysis of energy-reaction-diffusion systems - Fischer, Julian L; Hopf, Katharina; Kniely, Michael; Mielke, Alexander (SIAM Journal on Mathematical Analysis)
We establish global-in-time existence results for thermodynamically consistent reaction-(cross-)diffusion systems coupled to an equation describing heat transfer. Our main interest is to model species-dependent diffusivities, while at the same time ensuring thermodynamic consistency. A key difficulty of the non-isothermal case lies in the intrinsic presence of cross-diffusion type phenomena like the Soret and the Dufour effect: due to the temperature/energy dependence of the thermodynamic equilibria, a nonvanishing temperature gradient may drive a concentration flux even in a situation with constant concentrations; likewise, a nonvanishing concentration gradient may drive a heat flux even in a case of spatially constant temperature. We use time discretisation and regularisation techniques and derive a priori estimates based on a suitable entropy and the associated entropy production. Renormalised solutions are used in cases where non-integrable diffusion fluxes or reaction terms appear.
Keywords: Energy-Reaction-Diffusion Systems; Cross Diffusion; Global-In-Time Existence of Weak/Renormalised Solutions; Entropy Method; Onsager System; Soret/Dufour Effect

A secret source - Higginbotham, Andrew P (Nature Physics)
Superconducting devices ubiquitously have an excess of broken Cooper pairs, which can hamper their performance. It is widely believed that external radiation is responsible but a study now suggests there must be an additional, unknown source.
Keywords: superconducting devices; superconducting properties and materials

Why did the Wolbachia transinfection cross the road? Drift, deterministic dynamics, and disease control - Turelli, Michael; Barton, Nicholas H (Evolution Letters)
Maternally inherited Wolbachia transinfections are being introduced into natural mosquito populations to reduce the transmission of dengue, Zika, and other arboviruses. Wolbachia-induced cytoplasmic incompatibility provides a frequency-dependent reproductive advantage to infected females that can spread transinfections within and among populations. However, because transinfections generally reduce host fitness, they tend to spread within populations only after their frequency exceeds a critical threshold. This produces bistability with stable equilibrium frequencies at both 0 and 1, analogous to the bistability produced by underdominance between alleles or karyotypes and by population dynamics under Allee effects. Here, we analyze how stochastic frequency variation produced by finite population size can facilitate the local spread of variants with bistable dynamics into areas where invasion is unexpected from deterministic models. Our exemplar is the establishment of wMel Wolbachia in the Aedes aegypti population of Pyramid Estates (PE), a small community in far north Queensland, Australia. In 2011, wMel was stably introduced into Gordonvale, separated from PE by barriers to A. aegypti dispersal. After nearly 6 years during which wMel was observed only at low frequencies in PE, corresponding to an apparent equilibrium between immigration and selection, wMel rose to fixation by 2018. Using analytic approximations and statistical analyses, we demonstrate that the observed fixation of wMel at PE is consistent with both stochastic transition past an unstable threshold frequency and deterministic transformation produced by steady immigration at a rate just above the threshold required for deterministic invasion. The indeterminacy results from a delicate balance of parameters needed to produce the delayed transition observed. Our analyses suggest that once Wolbachia transinfections are established locally through systematic introductions, stochastic “threshold crossing” is likely to only minimally enhance spatial spread, providing a local ratchet that slightly—but systematically—aids area-wide transformation of disease-vector populations in heterogeneous landscapes.
Keywords: genetics; ecology; evolution; behavior and systematics

The Orthobunyavirus Germiston enters host cells from late endosomes - Windhaber, Stefan; Xin, Qilin; Uckeley, Zina M.; Koch, Jana; Obr, Martin; Garnier, Céline; Luengo-Guyonnot, Catherine; Duboeuf, Maëva; Schur, Florian KM; Lozach, Pierre-Yves (Journal of Virology)
With more than 80 members worldwide, the Orthobunyavirus genus in the Peribunyaviridae family is a large genus of enveloped RNA viruses, many of which are emerging pathogens in humans and livestock. How orthobunyaviruses (OBVs) penetrate and infect mammalian host cells remains poorly characterized. Here, we investigated the entry mechanisms of the OBV Germiston (GERV). Viral particles were visualized by cryo-electron microscopy and appeared roughly spherical with an average diameter of 98 nm. Labeling of the virus with fluorescent dyes did not adversely affect its infectivity and allowed the monitoring of single particles in fixed and live cells. Using this approach, we found that endocytic internalization of bound viruses was asynchronous and occurred within 30-40 min. The virus entered Rab5a+ early endosomes and, subsequently, late endosomal vacuoles containing Rab7a but not LAMP-1. Infectious entry did not require proteolytic cleavage, and endosomal acidification was sufficient and necessary for viral fusion. Acid-activated penetration began 15-25 min after initiation of virus internalization and relied on maturation of early endosomes to late endosomes. The optimal pH for viral membrane fusion was slightly below 6.0, and penetration was hampered when the potassium influx was abolished. Overall, our study provides real-time visualization of GERV entry into host cells and demonstrates the importance of late endosomal maturation in facilitating OBV penetration.
Keywords: virology; insect science; immunology; microbiology

Local stability of ground states in locally gapped and weakly interacting quantum spin systems - Henheik, Sven Joscha; Teufel, Stefan; Wessel, Tom (Letters in Mathematical Physics)
Based on a result by Yarotsky (J Stat Phys 118, 2005), we prove that localized but otherwise arbitrary perturbations of weakly interacting quantum spin systems with uniformly gapped on-site terms change the ground state of such a system only locally, even if they close the spectral gap. We call this a strong version of the local perturbations perturb locally (LPPL) principle which is known to hold for much more general gapped systems, but only for perturbations that do not close the spectral gap of the Hamiltonian. We also extend this strong LPPL-principle to Hamiltonians that have the appropriate structure of gapped on-site terms and weak interactions only locally in some region of space. While our results are technically corollaries to a theorem of Yarotsky, we expect that the paradigm of systems with a locally gapped ground state that is completely insensitive to the form of the Hamiltonian elsewhere extends to other situations and has important physical consequences.
Keywords: mathematical physics; statistical and nonlinear physics

Adiabatic theorem in the thermodynamic limit: Systems with a gap in the bulk - Henheik, Sven Joscha; Teufel, Stefan (Forum of Mathematics, Sigma)
We prove a generalised super-adiabatic theorem for extended fermionic systems assuming a spectral gap only in the bulk. More precisely, we assume that the infinite system has a unique ground state and that the corresponding Gelfand–Naimark–Segal Hamiltonian has a spectral gap above its eigenvalue zero. Moreover, we show that a similar adiabatic theorem also holds in the bulk of finite systems up to errors that vanish faster than any inverse power of the system size, although the corresponding finite-volume Hamiltonians need not have a spectral gap.
Keywords: computational mathematics; discrete mathematics and combinatorics; geometry and topology; mathematical physics; statistics and probability; algebra and number theory; theoretical computer science; analysis

The BCS critical temperature at high density - Henheik, Sven Joscha (Mathematical Physics, Analysis and Geometry)
We investigate the BCS critical temperature Tc in the high-density limit and derive an asymptotic formula, which strongly depends on the behavior of the interaction potential V on the Fermi-surface. Our results include a rigorous confirmation for the behavior of Tc at high densities proposed by Langmann et al. (Phys Rev Lett 122:157001, 2019) and identify precise conditions under which superconducting domes arise in BCS theory.
Keywords: geometry and topology; mathematical physics

Wolbachia frequency data from: Why did the Wolbachia transinfection cross the road? Drift, deterministic dynamics and disease control - Turelli, Michael; Barton, Nicholas H
Maternally inherited Wolbachia transinfections are being introduced into natural mosquito populations to reduce the transmission of dengue, Zika and other arboviruses. Wolbachia-induced cytoplasmic incompatibility provides a frequency-dependent reproductive advantage to infected females that can spread transinfections within and among populations. However, because transinfections generally reduce host fitness, they tend to spread within populations only after their frequency exceeds a critical threshold. This produces bistability with stable equilibrium frequencies at both 0 and 1, analogous to the bistability produced by underdominance between alleles or karyotypes and by population dynamics under Allee effects. Here, we analyze how stochastic frequency variation produced by finite population size can facilitate the local spread of variants with bistable dynamics into areas where invasion is unexpected from deterministic models. Our exemplar is the establishment of wMel Wolbachia in the Aedes aegypti population of Pyramid Estates (PE), a small community in far north Queensland, Australia. In 2011, wMel was stably introduced into Gordonvale, separated from PE by barriers to Ae. aegypti dispersal. After nearly six years during which wMel was observed only at low frequencies in PE, corresponding to an apparent equilibrium between immigration and selection, wMel rose to fixation by 2018. Using analytic approximations and statistical analyses, we demonstrate that the observed fixation of wMel at PE is consistent with both stochastic transition past an unstable threshold frequency and deterministic transformation produced by steady immigration at a rate just above the threshold required for deterministic invasion. The indeterminacy results from a delicate balance of parameters needed to produce the delayed transition observed. Our analyses suggest that once Wolbachia transinfections are established locally through systematic introductions, stochastic “threshold crossing” is likely to only minimally enhance spatial spread, providing a local ratchet that slightly – but systematically – aids area-wide transformation of disease-vector populations in heterogeneous landscapes.
Keywords: Biological sciences

Shear-convection interactions and orientation of tropical squall lines - Abramian, Sophie; Muller, Caroline J; Risi, Camille (Geophysical Research Letters)
Squall lines are known to be the consequence of the interaction of low-level shear with cold pools associated with convective downdrafts. Also, as the magnitude of the shear increases beyond a critical shear, squall lines tend to orient themselves. The existing literature suggests that this orientation reduces incoming wind shear to the squall line, and maintains equilibrium between wind shear and cold pool spreading. Although this theory is widely accepted, very few quantitative studies have been conducted on supercritical regime especially. Here, we test this hypothesis with tropical squall lines obtained by imposing a vertical wind shear in cloud resolving simulations in radiative convective equilibrium. In the sub-critical regime, squall lines are perpendicular to the shear. In the super-critical regime, their orientation maintain the equilibrium, supporting existing theories. We also find that as shear increases, cold pools become more intense. However, this intensification has little impact on squall line orientation.

Phase transition to turbulence in spatially extended shear flows - Klotz, Lukasz; Lemoult, Grégoire M; Avila, Kerstin; Hof, Björn (Physical Review Letters)
Directed percolation (DP) has recently emerged as a possible solution to the century old puzzle surrounding the transition to turbulence. Multiple model studies reported DP exponents, however, experimental evidence is limited since the largest possible observation times are orders of magnitude shorter than the flows’ characteristic timescales. An exception is cylindrical Couette flow where the limit is not temporal, but rather the realizable system size. We present experiments in a Couette setup of unprecedented azimuthal and axial aspect ratios. Approaching the critical point to within less than 0.1% we determine five critical exponents, all of which are in excellent agreement with the 2+1D DP universality class. The complex dynamics encountered at the onset of turbulence can hence be fully rationalized within the framework of statistical mechanics.

Very stable Higgs bundles, equivariant multiplicity and mirror symmetry - Hausel, Tamás; Hitchin, Nigel (Inventiones Mathematicae)
We define and study the existence of very stable Higgs bundles on Riemann surfaces, how it implies a precise formula for the multiplicity of the very stable components of the global nilpotent cone and its relationship to mirror symmetry. The main ingredients are the Bialynicki-Birula theory of C∗-actions on semiprojective varieties, C∗ characters of indices of C∗-equivariant coherent sheaves, Hecke transformation for Higgs bundles, relative Fourier–Mukai transform along the Hitchin fibration, hyperholomorphic structures on universal bundles and cominuscule Higgs bundles.

Rigidity transitions in development and disease - Hannezo, Edouard B; Heisenberg, Carl-Philipp J (Trends in Cell Biology)
Although rigidity and jamming transitions have been widely studied in physics and material science, their importance in a number of biological processes, including embryo development, tissue homeostasis, wound healing, and disease progression, has only begun to be recognized in the past few years. The hypothesis that biological systems can undergo rigidity/jamming transitions is attractive, as it would allow these systems to change their material properties rapidly and strongly. However, whether such transitions indeed occur in biological systems, how they are being regulated, and what their physiological relevance might be, is still being debated. Here, we review theoretical and experimental advances from the past few years, focusing on the regulation and role of potential tissue rigidity transitions in different biological processes.

Blood-based epigenome-wide analyses of cognitive abilities - McCartney, Daniel L.; Hillary, Robert F.; Conole, Eleanor L.S.; Banos, Daniel Trejo; Gadd, Danni A.; Walker, Rosie M.; Nangle, Cliff; Flaig, Robin; Campbell, Archie; Murray, Alison D.; Maniega, Susana Muñoz; Valdés-Hernández, María Del C.; et al. (Genome Biology)
Background: Blood-based markers of cognitive functioning might provide an accessible way to track neurodegeneration years prior to clinical manifestation of cognitive impairment and dementia. Results: Using blood-based epigenome-wide analyses of general cognitive function, we show that individual differences in DNA methylation (DNAm) explain 35.0% of the variance in general cognitive function (g). A DNAm predictor explains ~4% of the variance, independently of a polygenic score, in two external cohorts. It also associates with circulating levels of neurology- and inflammation-related proteins, global brain imaging metrics, and regional cortical volumes. Conclusions: As sample sizes increase, the ability to assess cognitive function from DNAm data may be informative in settings where cognitive testing is unreliable or unavailable.

Predicting bacterial promoter function and evolution from random sequences - Lagator, Mato; Sarikas, Srdjan; Steinrueck, Magdalena; Toledo-Aparicio, David; Bollback, Jonathan P; Guet, Calin C; Tkačik, Gašper (eLife)
Predicting function from sequence is a central problem of biology. Currently, this is possible only locally in a narrow mutational neighborhood around a wildtype sequence rather than globally from any sequence. Using random mutant libraries, we developed a biophysical model that accounts for multiple features of σ70 binding bacterial promoters to predict constitutive gene expression levels from any sequence. We experimentally and theoretically estimated that 10–20% of random sequences lead to expression and ~80% of non-expressing sequences are one mutation away from a functional promoter. The potential for generating expression from random sequences is so pervasive that selection acts against σ70-RNA polymerase binding sites even within inter-genic, promoter-containing regions. This pervasiveness of σ70-binding sites implies that emergence of promoters is not the limiting step in gene regulatory evolution. Ultimately, the inclusion of novel features of promoter function into a mechanistic model enabled not only more accurate predictions of gene expression levels, but also identified that promoters evolve more rapidly than previously thought.

The solute carrier MFSD1 decreases β1 integrin’s activation status and thus tumor metastasis - Roblek, Marko; Bicher, Julia; van Gogh, Merel; György, Attila; Seeböck, Rita; Szulc, Bozena; Damme, Markus; Olczak, Mariusz; Borsig, Lubor; Siekhaus, Daria E (Frontiers in Oncology)
Solute carriers are increasingly recognized as participating in a plethora of pathologies, including cancer. We describe here the involvement of the orphan solute carrier MFSD1 in the regulation of tumor cell migration. Loss of MFSD1 enabled higher levels of metastasis in a mouse model. We identified an increased migratory potential in MFSD1-/- tumor cells which was mediated by increased focal adhesion turn-over, reduced stability of mature inactive β1 integrin, and the resulting increased integrin activation index. We show that MFSD1 promoted recycling to the cell surface of endocytosed inactive β1 integrin and thereby protected β1 integrin from proteolytic degradation; this led to dampening of the integrin activation index. Furthermore, down-regulation of MFSD1 expression was observed during early steps of tumorigenesis and higher MFSD1 expression levels correlate with a better cancer patient prognosis. In sum, we describe a requirement for endolysosomal MFSD1 in efficient β1 integrin recycling to suppress tumor spread.

Auxin analog-induced Ca2+ signaling is independent of inhibition of endosomal aggregation in Arabidopsis roots - Wang, R; Himschoot, E; Grenzi, M; Chen, J; Safi, A; Krebs, M; Schumacher, K; Nowack, MK; Moeder, W; Yoshioka, K; Van Damme, D; De Smet, I; et al. (Journal of Experimental Botany)
Much of what we know about the role of auxin in plant development derives from exogenous manipulations of auxin distribution and signaling, using inhibitors, auxins and auxin analogs. In this context, synthetic auxin analogs, such as 1-Naphtalene Acetic Acid (1-NAA), are often favored over the endogenous auxin indole-3-acetic acid (IAA), in part due to their higher stability. While such auxin analogs have proven to be instrumental to reveal the various faces of auxin, they display in some cases distinct bioactivities compared to IAA. Here, we focused on the effect of auxin analogs on the accumulation of PIN proteins in Brefeldin A-sensitive endosomal aggregations (BFA bodies), and the correlation with the ability to elicit Ca 2+ responses. For a set of commonly used auxin analogs, we evaluated if auxin-analog induced Ca 2+ signaling inhibits PIN accumulation. Not all auxin analogs elicited a Ca 2+ response, and their differential ability to elicit Ca 2+ responses correlated partially with their ability to inhibit BFA-body formation. However, in tir1/afb and cngc14, 1-NAA-induced Ca 2+ signaling was strongly impaired, yet 1-NAA still could inhibit PIN accumulation in BFA bodies. This demonstrates that TIR1/AFB-CNGC14-dependent Ca 2+ signaling does not inhibit BFA body formation in Arabidopsis roots.

A translation control module coordinates germline stem cell differentiation with ribosome biogenesis during Drosophila oogenesis - Martin, Elliot T.; Blatt, Patrick; Ngyuen, Elaine; Lahr, Roni; Selvam, Sangeetha; Yoon, Hyun Ah M.; Pocchiari, Tyler; Emtenani, Shamsi; Siekhaus, Daria E; Berman, Andrea; Fuchs, Gabriele; Rangan, Prashanth (Developmental Cell)
Ribosomal defects perturb stem cell differentiation, causing diseases called ribosomopathies. How ribosome levels control stem cell differentiation is not fully known. Here, we discovered three RNA helicases are required for ribosome biogenesis and for Drosophila oogenesis. Loss of these helicases, which we named Aramis, Athos and Porthos, lead to aberrant stabilization of p53, cell cycle arrest and stalled GSC differentiation. Unexpectedly, Aramis is required for efficient translation of a cohort of mRNAs containing a 5’-Terminal-Oligo-Pyrimidine (TOP)-motif, including mRNAs that encode ribosomal proteins and a conserved p53 inhibitor, Novel Nucleolar protein 1 (Non1). The TOP-motif co-regulates the translation of growth-related mRNAs in mammals. As in mammals, the La-related protein co-regulates the translation of TOP-motif containing RNAs during Drosophila oogenesis. Thus, a previously unappreciated TOP-motif in Drosophila responds to reduced ribosome biogenesis to co-regulate the translation of ribosomal proteins and a p53 repressor, thus coupling ribosome biogenesis to GSC differentiation.

Cell division in tissues enables macrophage infiltration - Akhmanova, Maria; Emtenani, Shamsi; Krueger, Daniel; György, Attila; Pereira Guarda, Mariana; Vlasov, Mikhail; Vlasov, Fedor; Akopian, Andrei; Ratheesh, Aparna; De Renzis, Stefano; Siekhaus, Daria E (Science)
Cells migrate through crowded microenvironments within tissues during normal development, immune response, and cancer metastasis. Although migration through pores and tracks in the extracellular matrix (ECM) has been well studied, little is known about cellular traversal into confining cell-dense tissues. We find that embryonic tissue invasion by Drosophila macrophages requires division of an epithelial ectodermal cell at the site of entry. Dividing ectodermal cells disassemble ECM attachment formed by integrin-mediated focal adhesions next to mesodermal cells, allowing macrophages to move their nuclei ahead and invade between two immediately adjacent tissues. Invasion efficiency depends on division frequency, but reduction of adhesion strength allows macrophage entry independently of division. This work demonstrates that tissue dynamics can regulate cellular infiltration.

Auxin signaling: Research advances over the past 30 years - Yu, Z; Zhang, F; Friml, Jiří; Ding, Z (Journal of Integrative Plant Biology)
Auxin, one of the first identified and most widely studied phytohormones, has been and will remain a hot topic in plant biology. After more than a century of passionate exploration, the mysteries of its synthesis, transport, signaling, and metabolism have largely been unlocked. Due to the rapid development of new technologies, new methods, and new genetic materials, the study of auxin has entered the fast lane over the past 30 years. Here, we highlight advances in understanding auxin signaling, including auxin perception, rapid auxin responses, TRANSPORT INHIBITOR RESPONSE 1 and AUXIN SIGNALING F-boxes (TIR1/AFBs)-mediated transcriptional and non-transcriptional branches, and the epigenetic regulation of auxin signaling. We also focus on feedback inhibition mechanisms that prevent the over-amplification of auxin signals. In addition, we cover the TRANSMEMBRANE KINASEs (TMKs)-mediated non-canonical signaling, which converges with TIR1/AFBs-mediated transcriptional regulation to coordinate plant growth and development. The identification of additional auxin signaling components and their regulation will continue to open new avenues of research in this field, leading to an increasingly deeper, more comprehensive understanding of how auxin signals are interpreted at the cellular level to regulate plant growth and development.

Combining pattern-based CRFs and weighted context-free grammars - Takhanov, Rustem; Kolmogorov, Vladimir (Intelligent Data Analysis)
We consider two models for the sequence labeling (tagging) problem. The first one is a Pattern-Based Conditional Random Field (PB), in which the energy of a string (chain labeling) x=x1⁢…⁢xn∈Dn is a sum of terms over intervals [i,j] where each term is non-zero only if the substring xi⁢…⁢xj equals a prespecified word w∈Λ. The second model is a Weighted Context-Free Grammar (WCFG) frequently used for natural language processing. PB and WCFG encode local and non-local interactions respectively, and thus can be viewed as complementary. We propose a Grammatical Pattern-Based CRF model (GPB) that combines the two in a natural way. We argue that it has certain advantages over existing approaches such as the Hybrid model of Benedí and Sanchez that combines N-grams and WCFGs. The focus of this paper is to analyze the complexity of inference tasks in a GPB such as computing MAP. We present a polynomial-time algorithm for general GPBs and a faster version for a special case that we call Interaction Grammars.

Physiological synaptic activity and recognition memory require astroglial glutamine - Cheung, Giselle T; Bataveljic, Danijela; Visser, Josien; Kumar, Naresh; Moulard, Julien; Dallérac, Glenn; Mozheiko, Daria; Rollenhagen, Astrid; Ezan, Pascal; Mongin, Cédric; Chever, Oana; Bemelmans, Alexis Pierre; et al. (Nature Communications)
Presynaptic glutamate replenishment is fundamental to brain function. In high activity regimes, such as epileptic episodes, this process is thought to rely on the glutamate-glutamine cycle between neurons and astrocytes. However the presence of an astroglial glutamine supply, as well as its functional relevance in vivo in the healthy brain remain controversial, partly due to a lack of tools that can directly examine glutamine transfer. Here, we generated a fluorescent probe that tracks glutamine in live cells, which provides direct visual evidence of an activity-dependent glutamine supply from astroglial networks to presynaptic structures under physiological conditions. This mobilization is mediated by connexin43, an astroglial protein with both gap-junction and hemichannel functions, and is essential for synaptic transmission and object recognition memory. Our findings uncover an indispensable recruitment of astroglial glutamine in physiological synaptic activity and memory via an unconventional pathway, thus providing an astrocyte basis for cognitive processes.

Infection dynamics of COVID-19 virus under lockdown and reopening - Svoboda, Jakub; Tkadlec, Josef; Pavlogiannis, Andreas; Chatterjee, Krishnendu; Nowak, Martin A. (Scientific Reports)
Motivated by COVID-19, we develop and analyze a simple stochastic model for the spread of disease in human population. We track how the number of infected and critically ill people develops over time in order to estimate the demand that is imposed on the hospital system. To keep this demand under control, we consider a class of simple policies for slowing down and reopening society and we compare their efficiency in mitigating the spread of the virus from several different points of view. We find that in order to avoid overwhelming of the hospital system, a policy must impose a harsh lockdown or it must react swiftly (or both). While reacting swiftly is universally beneficial, being harsh pays off only when the country is patient about reopening and when the neighboring countries coordinate their mitigation efforts. Our work highlights the importance of acting decisively when closing down and the importance of patience and coordination between neighboring countries when reopening.

Mechanisms underlying TARP modulation of the GluA1/2-γ8 AMPA receptor - Herguedas, Beatriz; Kohegyi, Bianka K.; Dohrke, Jan Niklas; Watson, Jake; Zhang, Danyang; Ho, Hinze; Shaikh, Saher A.; Lape, Remigijus; Krieger, James M.; Greger, Ingo H. (Nature Communications)
AMPA-type glutamate receptors (AMPARs) mediate rapid signal transmission at excitatory synapses in the brain. Glutamate binding to the receptor’s ligand-binding domains (LBDs) leads to ion channel activation and desensitization. Gating kinetics shape synaptic transmission and are strongly modulated by transmembrane AMPAR regulatory proteins (TARPs) through currently incompletely resolved mechanisms. Here, electron cryo-microscopy structures of the GluA1/2 TARP-γ8 complex, in both open and desensitized states (at 3.5 Å), reveal state-selective engagement of the LBDs by the large TARP-γ8 loop (‘β1’), elucidating how this TARP stabilizes specific gating states. We further show how TARPs alter channel rectification, by interacting with the pore helix of the selectivity filter. Lastly, we reveal that the Q/R-editing site couples the channel constriction at the filter entrance to the gate, and forms the major cation binding site in the conduction path. Our results provide a mechanistic framework of how TARPs modulate AMPAR gating and conductance.

Low-field magnetic anisotropy of Sr2IrO4 - Nauman, Muhammad; Hussain, Tayyaba; Choi, Joonyoung; Lee, Nara; Choi, Young Jai; Kang, Woun; Jo, Younjung (Journal of physics: Condensed matter)
Magnetic anisotropy in strontium iridate (Sr2IrO4) is essential because of its strong spin–orbit coupling and crystal field effect. In this paper, we present a detailed mapping of the out-of-plane (OOP) magnetic anisotropy in Sr2IrO4 for different sample orientations using torque magnetometry measurements in the low-magnetic-field region before the isospins are completely ordered. Dominant in-plane anisotropy was identified at low fields, confirming the b axis as an easy magnetization axis. Based on the fitting analysis of the strong uniaxial magnetic anisotropy, we observed that the main anisotropic effect arises from a spin–orbit-coupled magnetic exchange interaction affecting the OOP interaction. The effect of interlayer exchange interaction results in additional anisotropic terms owing to the tilting of the isospins. The results are relevant for understanding OOP magnetic anisotropy and provide a new way to analyze the effects of spin–orbit-coupling and interlayer magnetic exchange interactions. This study provides insight into the understanding of bulk magnetic, magnetotransport, and spintronic behavior on Sr2IrO4 for future studies.

Thermalisation for Wigner matrices - Cipolloni, Giorgio; Erdös, László; Schröder, Dominik J (Journal of Functional Analysis)
We compute the deterministic approximation of products of Sobolev functions of large Wigner matrices W and provide an optimal error bound on their fluctuation with very high probability. This generalizes Voiculescu's seminal theorem from polynomials to general Sobolev functions, as well as from tracial quantities to individual matrix elements. Applying the result to eitW for large t, we obtain a precise decay rate for the overlaps of several deterministic matrices with temporally well separated Heisenberg time evolutions; thus we demonstrate the thermalisation effect of the unitary group generated by Wigner matrices.

Intruders cooperatively interact with a wall into granular matter - Espinosa, M.; Diaz Melian, Vicente L; Serrano-Muñoz, A.; Altshuler, E. (Granular Matter)
When a cylindrical object penetrates granular matter near a vertical boundary, it experiences two effects: its center of mass moves horizontally away from the wall, and it rotates around its symmetry axis. Here we show experimentally that, if two identical intruders instead of one are released side-by-side near the wall, both effects are also detected. However, unexpected phenomena appear due to a cooperative dynamics between the intruders. The net horizontal distance traveled by the common center of mass of the twin intruders is much larger than that traveled by one intruder released at the same initial distance from the wall, and the rotation is also larger. The experimental results are well described by the Discrete Element Method (DEM), which reveals that, as the number of intruders horizontally released side-by-side increases, the total energy dissipation per intruder decreases. Finally, DEM simulations demonstrate that the horizontal repulsion is substantially enhanced if groups of intruders are released forming a column near the wall.
Keywords: granular matter; boundary effects; intruder penetration; sedimentation

Arithmetic purity of the Hardy-Littlewood property and geometric sieve for affine quadrics - Cao, Yang; Huang, Zhizhong (Advances in Mathematics)
We establish the Hardy-Littlewood property (à la Borovoi-Rudnick) for Zariski open subsets in affine quadrics of the form q(x1,...,xn)=m, where q is a non-degenerate integral quadratic form in n>3 variables and m is a non-zero integer. This gives asymptotic formulas for the density of integral points taking coprime polynomial values, which is a quantitative version of the arithmetic purity of strong approximation property off infinity for affine quadrics.

Tension-dependent stabilization of E-cadherin limits cell-cell contact expansion in zebrafish germ-layer progenitor cells - Slovakova, Jana; Sikora, Mateusz K; Arslan, Feyza N; Caballero Mancebo, Silvia; Krens, Gabriel; Kaufmann, Walter; Merrin, Jack; Heisenberg, Carl-Philipp J (Proceedings of the National Academy of Sciences of the United States of America)
Tension of the actomyosin cell cortex plays a key role in determining cell–cell contact growth and size. The level of cortical tension outside of the cell–cell contact, when pulling at the contact edge, scales with the total size to which a cell–cell contact can grow [J.-L. Maître et al., Science 338, 253–256 (2012)]. Here, we show in zebrafish primary germ-layer progenitor cells that this monotonic relationship only applies to a narrow range of cortical tension increase and that above a critical threshold, contact size inversely scales with cortical tension. This switch from cortical tension increasing to decreasing progenitor cell–cell contact size is caused by cortical tension promoting E-cadherin anchoring to the actomyosin cytoskeleton, thereby increasing clustering and stability of E-cadherin at the contact. After tension-mediated E-cadherin stabilization at the contact exceeds a critical threshold level, the rate by which the contact expands in response to pulling forces from the cortex sharply drops, leading to smaller contacts at physiologically relevant timescales of contact formation. Thus, the activity of cortical tension in expanding cell–cell contact size is limited by tension-stabilizing E-cadherin–actin complexes at the contact.

Novel patterns of expression and recruitment of new genes on the t-haplotype, a mouse selfish chromosome - Kelemen, Réka K; Elkrewi, Marwan N; Lindholm, Anna K.; Vicoso, Beatriz (Proceedings of the Royal Society B: Biological Sciences)
The t-haplotype of mice is a classical model for autosomal transmission distortion. A largely non-recombining variant of the proximal region of chromosome 17, it is transmitted to more than 90% of the progeny of heterozygous males through the disabling of sperm carrying a standard chromosome. While extensive genetic and functional work has shed light on individual genes involved in drive, much less is known about the evolution and function of the rest of its hundreds of genes. Here, we characterize the sequence and expression of dozens of t-specific transcripts and of their chromosome 17 homologues. Many genes showed reduced expression of the t-allele, but an equal number of genes showed increased expression of their t-copy, consistent with increased activity or a newly evolved function. Genes on the t-haplotype had a significantly higher non-synonymous substitution rate than their homologues on the standard chromosome, with several genes harbouring dN/dS ratios above 1. Finally, the t-haplotype has acquired at least two genes from other chromosomes, which show high and tissue-specific expression. These results provide a first overview of the gene content of this selfish element, and support a more dynamic evolutionary scenario than expected of a large genomic region with almost no recombination.

Auxin canalization: From speculative models toward molecular players - Hajny, Jakub; Tan, Shutang; Friml, Jiří (Current Opinion in Plant Biology)
Among the most fascinated properties of the plant hormone auxin is its ability to promote formation of its own directional transport routes. These gradually narrowing auxin channels form from the auxin source toward the sink and involve coordinated, collective polarization of individual cells. Once established, the channels provide positional information, along which new vascular strands form, for example, during organogenesis, regeneration, or leave venation. The main prerequisite of this still mysterious auxin canalization mechanism is a feedback between auxin signaling and its directional transport. This is manifested by auxin-induced re-arrangements of polar, subcellular localization of PIN-FORMED (PIN) auxin exporters. Immanent open questions relate to how position of auxin source and sink as well as tissue context are sensed and translated into tissue polarization and how cells communicate to polarize coordinately. Recently, identification of the first molecular players opens new avenues into molecular studies of this intriguing example of self-organizing plant development.

Mirror symmetry for the Tate curve via tropical and log corals - Arguez, Nuroemuer Huelya (Journal of the London Mathematical Society)
We introduce tropical corals, balanced trees in a half-space, and show that they correspond to holomorphic polygons capturing the product rule in Lagrangian Floer theory for the elliptic curve. We then prove a correspondence theorem equating counts of tropical corals to punctured log Gromov–Witten invariants of the Tate curve. This implies that the homogeneous coordinate ring of the mirror to the Tate curve is isomorphic to the degree-zero part of symplectic cohomology, confirming a prediction of homological mirror symmetry.

Overcoming rare-language discrimination in multi-lingual sentiment analysis - Lampert, Jasmin; Lampert, Christoph (2021 IEEE International Conference on Big Data)
The digitalization of almost all aspects of our everyday lives has led to unprecedented amounts of data being freely available on the Internet. In particular social media platforms provide rich sources of user-generated data, though typically in unstructured form, and with high diversity, such as written in many different languages. Automatically identifying meaningful information in such big data resources and extracting it efficiently is one of the ongoing challenges of our time. A common step for this is sentiment analysis, which forms the foundation for tasks such as opinion mining or trend prediction. Unfortunately, publicly available tools for this task are almost exclusively available for English-language texts. Consequently, a large fraction of the Internet users, who do not communicate in English, are ignored in automatized studies, a phenomenon called rare-language discrimination.In this work we propose a technique to overcome this problem by a truly multi-lingual model, which can be trained automatically without linguistic knowledge or even the ability to read the many target languages. The main step is to combine self-annotation, specifically the use of emoticons as a proxy for labels, with multi-lingual sentence representations.To evaluate our method we curated several large datasets from data obtained via the free Twitter streaming API. The results show that our proposed multi-lingual training is able to achieve sentiment predictions at the same quality level for rare languages as for frequent ones, and in particular clearly better than what mono-lingual training achieves on the same data.

Theory of chirality induced spin selectivity: Progress and challenges - Evers, Ferdinand; Aharony, Amnon; Bar-Gill, Nir; Entin-Wohlman, Ora; Hedegård, Per; Hod, Oded; Jelinek, Pavel; Kamieniarz, Grzegorz; Lemeshko, Mikhail; Michaeli, Karen; Mujica, Vladimiro; Naaman, Ron; et al. (Advanced Materials)
A critical overview of the theory of the chirality-induced spin selectivity (CISS) effect, that is, phenomena in which the chirality of molecular species imparts significant spin selectivity to various electron processes, is provided. Based on discussions in a recently held workshop, and further work published since, the status of CISS effects—in electron transmission, electron transport, and chemical reactions—is reviewed. For each, a detailed discussion of the state-of-the-art in theoretical understanding is provided and remaining challenges and research opportunities are identified.

Defect engineering in solution-processed polycrystalline SnSe leads to high thermoelectric performance - Liu, Yu; Calcabrini, Mariano; Yu, Yuan; Lee, Seungho; Chang, Cheng; David, Jérémy; Ghosh, Tanmoy; Spadaro, Maria Chiara; Xie, Chenyang; Cojocaru-Mirédin, Oana; Arbiol, Jordi; Ibáñez, Maria (ACS Nano)
SnSe has emerged as one of the most promising materials for thermoelectric energy conversion due to its extraordinary performance in its single-crystal form and its low-cost constituent elements. However, to achieve an economic impact, the polycrystalline counterpart needs to replicate the performance of the single crystal. Herein, we optimize the thermoelectric performance of polycrystalline SnSe produced by consolidating solution-processed and surface-engineered SnSe particles. In particular, the SnSe particles are coated with CdSe molecular complexes that crystallize during the sintering process, forming CdSe nanoparticles. The presence of CdSe nanoparticles inhibits SnSe grain growth during the consolidation step due to Zener pinning, yielding a material with a high density of grain boundaries. Moreover, the resulting SnSe–CdSe nanocomposites present a large number of defects at different length scales, which significantly reduce the thermal conductivity. The produced SnSe–CdSe nanocomposites exhibit thermoelectric figures of merit up to 2.2 at 786 K, which is among the highest reported for solution-processed SnSe.
Keywords: tin selenide; nanocomposite; grain growth; Zener pinning; thermoelectricity; annealing; solution processing

Continuous and discrete radius functions on Voronoi tessellations and Delaunay mosaics - Biswas, Ranita; Cultrera Di Montesano, Sebastiano; Edelsbrunner, Herbert; Saghafian, Morteza (Discrete and Computational Geometry)
The Voronoi tessellation in Rd is defined by locally minimizing the power distance to given weighted points. Symmetrically, the Delaunay mosaic can be defined by locally maximizing the negative power distance to other such points. We prove that the average of the two piecewise quadratic functions is piecewise linear, and that all three functions have the same critical points and values. Discretizing the two piecewise quadratic functions, we get the alpha shapes as sublevel sets of the discrete function on the Delaunay mosaic, and analogous shapes as superlevel sets of the discrete function on the Voronoi tessellation. For the same non-critical value, the corresponding shapes are disjoint, separated by a narrow channel that contains no critical points but the entire level set of the piecewise linear function.

The physiology and genetics of bacterial responses to antibiotic combinations - Römhild, Roderich; Bollenbach, Mark Tobias; Andersson, Dan I. (Nature Reviews Microbiology)
Several promising strategies based on combining or cycling different antibiotics have been proposed to increase efficacy and counteract resistance evolution, but we still lack a deep understanding of the physiological responses and genetic mechanisms that underlie antibiotic interactions and the clinical applicability of these strategies. In antibiotic-exposed bacteria, the combined effects of physiological stress responses and emerging resistance mutations (occurring at different time scales) generate complex and often unpredictable dynamics. In this Review, we present our current understanding of bacterial cell physiology and genetics of responses to antibiotics. We emphasize recently discovered mechanisms of synergistic and antagonistic drug interactions, hysteresis in temporal interactions between antibiotics that arise from microbial physiology and interactions between antibiotics and resistance mutations that can cause collateral sensitivity or cross-resistance. We discuss possible connections between the different phenomena and indicate relevant research directions. A better and more unified understanding of drug and genetic interactions is likely to advance antibiotic therapy.
Keywords: General Immunology and Microbiology; Microbiology; Infectious Diseases

Barycentric cuts through a convex body - Patakova, Zuzana; Tancer, Martin; Wagner, Uli (Discrete and Computational Geometry)
Let K be a convex body in Rn (i.e., a compact convex set with nonempty interior). Given a point p in the interior of K, a hyperplane h passing through p is called barycentric if p is the barycenter of K∩h. In 1961, Grünbaum raised the question whether, for every K, there exists an interior point p through which there are at least n+1 distinct barycentric hyperplanes. Two years later, this was seemingly resolved affirmatively by showing that this is the case if p=p0 is the point of maximal depth in K. However, while working on a related question, we noticed that one of the auxiliary claims in the proof is incorrect. Here, we provide a counterexample; this re-opens Grünbaum’s question. It follows from known results that for n≥2, there are always at least three distinct barycentric cuts through the point p0∈K of maximal depth. Using tools related to Morse theory we are able to improve this bound: four distinct barycentric cuts through p0 are guaranteed if n≥3.

Cell surface fluctuations regulate early embryonic lineage sorting - Yanagida, Ayaka; Corujo-Simon, Elena; Revell, Christopher K.; Sahu, Preeti; Stirparo, Giuliano G.; Aspalter, Irene M.; Winkel, Alex K.; Peters, Ruby; De Belly, Henry; Cassani, Davide A.D.; Achouri, Sarra; Blumenfeld, Raphael; et al. (Cell)
In development, lineage segregation is coordinated in time and space. An important example is the mammalian inner cell mass, in which the primitive endoderm (PrE, founder of the yolk sac) physically segregates from the epiblast (EPI, founder of the fetus). While the molecular requirements have been well studied, the physical mechanisms determining spatial segregation between EPI and PrE remain elusive. Here, we investigate the mechanical basis of EPI and PrE sorting. We find that rather than the differences in static cell surface mechanical parameters as in classical sorting models, it is the differences in surface fluctuations that robustly ensure physical lineage sorting. These differential surface fluctuations systematically correlate with differential cellular fluidity, which we propose together constitute a non-equilibrium sorting mechanism for EPI and PrE lineages. By combining experiments and modeling, we identify cell surface dynamics as a key factor orchestrating the correct spatial segregation of the founder embryonic lineages.

Proteomic characterization of isolated Arabidopsis clathrin-coated vesicles reveals evolutionarily conserved and plant-specific components - Dahhan, DA; Reynolds, GD; Cárdenas, JJ; Eeckhout, D; Johnson, Alexander J; Yperman, K; Kaufmann, Walter; Vang, N; Yan, X; Hwang, I; Heese, A; De Jaeger, G; et al. (Plant Cell)
In eukaryotes, clathrin-coated vesicles (CCVs) facilitate the internalization of material from the cell surface as well as the movement of cargo in post-Golgi trafficking pathways. This diversity of functions is partially provided by multiple monomeric and multimeric clathrin adaptor complexes that provide compartment and cargo selectivity. The adaptor-protein assembly polypeptide-1 (AP-1) complex operates as part of the secretory pathway at the trans-Golgi network (TGN), while the AP-2 complex and the TPLATE complex jointly operate at the plasma membrane to execute clathrin-mediated endocytosis. Key to our further understanding of clathrin-mediated trafficking in plants will be the comprehensive identification and characterization of the network of evolutionarily conserved and plant-specific core and accessory machinery involved in the formation and targeting of CCVs. To facilitate these studies, we have analyzed the proteome of enriched TGN/early endosome-derived and endocytic CCVs isolated from dividing and expanding suspension-cultured Arabidopsis (Arabidopsis thaliana) cells. Tandem mass spectrometry analysis results were validated by differential chemical labeling experiments to identify proteins co-enriching with CCVs. Proteins enriched in CCVs included previously characterized CCV components and cargos such as the vacuolar sorting receptors in addition to conserved and plant-specific components whose function in clathrin-mediated trafficking has not been previously defined. Notably, in addition to AP-1 and AP-2, all subunits of the AP-4 complex, but not AP-3 or AP-5, were found to be in high abundance in the CCV proteome. The association of AP-4 with suspension-cultured Arabidopsis CCVs is further supported via additional biochemical data.

Impairing one sensory modality enhances another by reconfiguring peptidergic signalling in Caenorhabditis elegans - Valperga, Giulio; De Bono, Mario (eLife)
Animals that lose one sensory modality often show augmented responses to other sensory inputs. The mechanisms underpinning this cross-modal plasticity are poorly understood. We probe such mechanisms by performing a forward genetic screen for mutants with enhanced O2 perception in Caenorhabditis elegans. Multiple mutants exhibiting increased O2 responsiveness concomitantly show defects in other sensory responses. One mutant, qui-1, defective in a conserved NACHT/WD40 protein, abolishes pheromone-evoked Ca2+ responses in the ADL pheromone-sensing neurons. At the same time, ADL responsiveness to pre-synaptic input from O2-sensing neurons is heightened in qui-1, and other sensory defective mutants, resulting in enhanced neurosecretion although not increased Ca2+ responses. Expressing qui-1 selectively in ADL rescues both the qui-1 ADL neurosecretory phenotype and enhanced escape from 21% O2. Profiling ADL neurons in qui-1 mutants highlights extensive changes in gene expression, notably of many neuropeptide receptors. We show that elevated ADL expression of the conserved neuropeptide receptor NPR-22 is necessary for enhanced ADL neurosecretion in qui-1 mutants, and is sufficient to confer increased ADL neurosecretion in control animals. Sensory loss can thus confer cross-modal plasticity by changing the peptidergic connectome.

Field-effect transistor with a plasmonic fiber optic gate electrode as a multivariable biosensor device - Hasler, Roger; Reiner-Rozman, Ciril; Fossati, Stefan; Aspermair, Patrik; Dostalek, Jakub; Lee, Seungho; Ibáñez, Maria; Bintinger, Johannes; Knoll, Wolfgang (ACS Sensors)
A novel multivariable system, combining a transistor with fiber optic-based surface plasmon resonance spectroscopy with the gate electrode simultaneously acting as the fiber optic sensor surface, is reported. The dual-mode sensor allows for discrimination of mass and charge contributions for binding assays on the same sensor surface. Furthermore, we optimize the sensor geometry by investigating the influence of the fiber area to transistor channel area ratio and distance. We show that larger fiber optic tip diameters are favorable for electronic and optical signals and demonstrate the reversibility of plasmon resonance wavelength shifts after electric field application. As a proof of principle, a layer-by-layer assembly of polyelectrolytes is performed to benchmark the system against multivariable sensing platforms with planar surface plasmon resonance configurations. Furthermore, the biosensing performance is assessed using a thrombin binding assay with surface-immobilized aptamers as receptors, allowing for the detection of medically relevant thrombin concentrations.

High-pressure phase behaviors of titanium dioxide revealed by a Δ-learning potential - Lee, Jacob G.; Pickard, Chris J.; Cheng, Bingqing (The Journal of chemical physics)
Titanium dioxide has been extensively studied in the rutile or anatase phase, while its high-pressure phases are less well-understood, despite that many are thought to have interesting optical, mechanical, and electrochemical properties. First-principles methods, such as density functional theory (DFT), are often used to compute the enthalpies of TiO2 phases at 0 K, but they are expensive and, thus, impractical for long time scale and large system-size simulations at finite temperatures. On the other hand, cheap empirical potentials fail to capture the relative stabilities of various polymorphs. To model the thermodynamic behaviors of ambient and high-pressure phases of TiO2, we design an empirical model as a baseline and then train a machine learning potential based on the difference between the DFT data and the empirical model. This so-called Δ-learning potential contains long-range electrostatic interactions and predicts the 0 K enthalpies of stable TiO2 phases that are in good agreement with DFT. We construct a pressure–temperature phase diagram of TiO2 in the range 0 < P < 70 GPa and 100 < T < 1500 K. We then simulate dynamic phase transition processes by compressing anatase at different temperatures. At 300 K, we predominantly observe an anatase-to-baddeleyite transformation at about 20 GPa via a martensitic two-step mechanism with a highly ordered and collective atomic motion. At 2000 K, anatase can transform into cotunnite around 45–55 GPa in a thermally activated and probabilistic manner, accompanied by diffusive movement of oxygen atoms. The pressures computed for these transitions show good agreement with experiments. Our results shed light on how to synthesize and stabilize high-pressure TiO2 phases, and our method is generally applicable to other functional materials with multiple polymorphs.

The impact of changes in resolution on the persistent homology of images - Heiss, Teresa; Tymochko, Sarah; Story, Brittany; Garin, Adélie; Bui, Hoa; Bleile, Bea; Robins, Vanessa (2021 IEEE International Conference on Big Data)
Digital images enable quantitative analysis of material properties at micro and macro length scales, but choosing an appropriate resolution when acquiring the image is challenging. A high resolution means longer image acquisition and larger data requirements for a given sample, but if the resolution is too low, significant information may be lost. This paper studies the impact of changes in resolution on persistent homology, a tool from topological data analysis that provides a signature of structure in an image across all length scales. Given prior information about a function, the geometry of an object, or its density distribution at a given resolution, we provide methods to select the coarsest resolution yielding results within an acceptable tolerance. We present numerical case studies for an illustrative synthetic example and samples from porous materials where the theoretical bounds are unknown.

Field-effect transistor with a plasmonic fiber optic gate electrode as a multivariable biosensor device - Hasler, Roger; Reiner-Rozman, Ciril; Fossati, Stefan; Aspermair, Patrik; Dostalek, Jakub; Lee, Seungho; Ibáñez, Maria; Bintinger, Johannes; Knoll, Wolfgang
Detailed information about the data set see "dataset description.txt" file.

Functional John ellipsoids - Ivanov, Grigory; Naszódi, Márton (Journal of Functional Analysis)
We introduce a new way of representing logarithmically concave functions on Rd. It allows us to extend the notion of the largest volume ellipsoid contained in a convex body to the setting of logarithmically concave functions as follows. For every s>0, we define a class of non-negative functions on Rd derived from ellipsoids in Rd+1. For any log-concave function f on Rd , and any fixed s>0, we consider functions belonging to this class, and find the one with the largest integral under the condition that it is pointwise less than or equal to f, and we call it the John s-function of f. After establishing existence and uniqueness, we give a characterization of this function similar to the one given by John in his fundamental theorem. We find that John s-functions converge to characteristic functions of ellipsoids as s tends to zero and to Gaussian densities as s tends to infinity. As an application, we prove a quantitative Helly type result: the integral of the pointwise minimum of any family of log-concave functions is at least a constant cd multiple of the integral of the pointwise minimum of a properly chosen subfamily of size 3d+2, where cd depends only on d.

Proteome-wide cellular thermal shift assay reveals unexpected cross-talk between brassinosteroid and auxin signaling - Lu, Qing; Zhang, Yonghong; Hellner, Joakim; Giannini, Caterina; Xu, Xiangyu; Pauwels, Jarne; Ma, Qian; Dejonghe, Wim; Han, Huibin; Van De Cotte, Brigitte; Impens, Francis; Gevaert, Kris; et al. (Proceedings of the National Academy of Sciences of the United States of America)
Despite the growing interest in using chemical genetics in plant research, small molecule target identification remains a major challenge. The cellular thermal shift assay coupled with high-resolution mass spectrometry (CETSA MS) that monitors changes in the thermal stability of proteins caused by their interactions with small molecules, other proteins, or posttranslational modifications, allows the discovery of drug targets or the study of protein–metabolite and protein–protein interactions mainly in mammalian cells. To showcase the applicability of this method in plants, we applied CETSA MS to intact Arabidopsis thaliana cells and identified the thermal proteome of the plant-specific glycogen synthase kinase 3 (GSK3) inhibitor, bikinin. A comparison between the thermal and the phosphoproteomes of bikinin revealed the auxin efflux carrier PIN-FORMED1 (PIN1) as a substrate of the Arabidopsis GSK3s that negatively regulate the brassinosteroid signaling. We established that PIN1 phosphorylation by the GSK3s is essential for maintaining its intracellular polarity that is required for auxin-mediated regulation of vascular patterning in the leaf, thus revealing cross-talk between brassinosteroid and auxin signaling.

The number and distinct clustering patterns of voltage-gated Calcium channels in nerve terminals - Eguchi, Kohgaku; Montanaro-Punzengruber, Jacqueline-Claire; Le Monnier, Elodie; Shigemoto, Ryuichi (Frontiers in Neuroanatomy)
Upon the arrival of action potentials at nerve terminals, neurotransmitters are released from synaptic vesicles (SVs) by exocytosis. CaV2.1, 2.2, and 2.3 are the major subunits of the voltage-gated calcium channel (VGCC) responsible for increasing intraterminal calcium levels and triggering SV exocytosis in the central nervous system (CNS) synapses. The two-dimensional analysis of CaV2 distributions using sodium dodecyl sulfate (SDS)-digested freeze-fracture replica labeling (SDS-FRL) has revealed their numbers, densities, and nanoscale clustering patterns in individual presynaptic active zones. The variation in these properties affects the coupling of VGCCs with calcium sensors on SVs, synaptic efficacy, and temporal precision of transmission. In this study, we summarize how the morphological parameters of CaV2 distribution obtained using SDS-FRL differ depending on the different types of synapses and could correspond to functional properties in synaptic transmission.

Electron microscopic visualization of single molecules by tag-mediated metal particle labeling - Shigemoto, Ryuichi (Microscopy)
Genetically encoded tags have introduced extensive lines of application from purification of tagged proteins to their visualization at the single molecular, cellular, histological and whole-body levels. Combined with other rapidly developing technologies such as clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system, proteomics, super-resolution microscopy and proximity labeling, a large variety of genetically encoded tags have been developed in the last two decades. In this review, I focus on the current status of tag development for electron microscopic (EM) visualization of proteins with metal particle labeling. Compared with conventional immunoelectron microscopy using gold particles, tag-mediated metal particle labeling has several advantages that could potentially improve the sensitivity, spatial and temporal resolution, and applicability to a wide range of proteins of interest (POIs). It may enable researchers to detect single molecules in situ, allowing the quantitative measurement of absolute numbers and exact localization patterns of POI in the ultrastructural context. Thus, genetically encoded tags for EM could revolutionize the field as green fluorescence protein did for light microscopy, although we still have many challenges to overcome before reaching this goal.

Quantitative monitoring of software - Henzinger, Thomas A (Software Verification)
We present a formal framework for the online black-box monitoring of software using monitors with quantitative verdict functions. Quantitative verdict functions have several advantages. First, quantitative monitors can be approximate, i.e., the value of the verdict function does not need to correspond exactly to the value of the property under observation. Second, quantitative monitors can be quantified universally, i.e., for every possible observed behavior, the monitor tries to make the best effort to estimate the value of the property under observation. Third, quantitative monitors can watch boolean as well as quantitative properties, such as average response time. Fourth, quantitative monitors can use non-finite-state resources, such as counters. As a consequence, quantitative monitors can be compared according to how many resources they use (e.g., the number of counters) and how precisely they approximate the property under observation. This allows for a rich spectrum of cost-precision trade-offs in monitoring software.

Symmetry-allowed nonlinear orbital response across the topological phase transition in centrosymmetric materials - Davydova, Margarita; Serbyn, Maksym; Ishizuka, Hiroaki (Physical Review B)
Nonlinear optical responses are commonly used as a probe for studying the electronic properties of materials. For topological materials, studies thus far focused on photogalvanic electric currents, which are forbidden in centrosymmetric materials because they require broken inversion symmetry. In this Letter, we propose a class of symmetry-allowed responses for inversion-symmetric topological insulators with two doubly degenerate bands. We consider a specific example of such a response, the orbital current, and show that the sign of the response reflects the Z2 topological index, i.e., the orbital current changes sign at the transition between trivial and topological insulator phases. This is illustrated in two models of topological insulators: the Bernevig-Hughes-Zhang model and the 1T′ phase of transition metal dichalcogenides.

Macrophage mitochondrial bioenergetics and tissue invasion are boosted by an Atossa-Porthos axis in Drosophila - Emtenani, Shamsi; Martin, Elliot T; György, Attila; Bicher, Julia; Genger, Jakob-Wendelin; Köcher, Thomas; Akhmanova, Maria; Pereira Guarda, Mariana; Roblek, Marko; Bergthaler, Andreas; Hurd, Thomas R; Rangan, Prashanth; et al. (The Embo Journal)
Cellular metabolism must adapt to changing demands to enable homeostasis. During immune responses or cancer metastasis, cells leading migration into challenging environments require an energy boost, but what controls this capacity is unclear. Here, we study a previously uncharacterized nuclear protein, Atossa (encoded by CG9005), which supports macrophage invasion into the germband of Drosophila by controlling cellular metabolism. First, nuclear Atossa increases mRNA levels of Porthos, a DEAD-box protein, and of two metabolic enzymes, lysine-α-ketoglutarate reductase (LKR/SDH) and NADPH glyoxylate reductase (GR/HPR), thus enhancing mitochondrial bioenergetics. Then Porthos supports ribosome assembly and thereby raises the translational efficiency of a subset of mRNAs, including those affecting mitochondrial functions, the electron transport chain, and metabolism. Mitochondrial respiration measurements, metabolomics, and live imaging indicate that Atossa and Porthos power up OxPhos and energy production to promote the forging of a path into tissues by leading macrophages. Since many crucial physiological responses require increases in mitochondrial energy output, this previously undescribed genetic program may modulate a wide range of cellular behaviors.

Dynamics of hole singlet-triplet qubits with large g-factor differences - Jirovec, Daniel; Mutter, Philipp M.; Hofmann, Andrea C; Crippa, Alessandro; Rychetsky, Marek; Craig, David L.; Kukucka, Josip; Martins, Frederico; Ballabio, Andrea; Ares, Natalia; Chrastina, Daniel; Isella, Giovanni; et al. (Physical Review Letters)
The spin-orbit interaction permits to control the state of a spin qubit via electric fields. For holes it is particularly strong, allowing for fast all electrical qubit manipulation, and yet an in-depth understanding of this interaction in hole systems is missing. Here we investigate, experimentally and theoretically, the effect of the cubic Rashba spin-orbit interaction on the mixing of the spin states by studying singlet-triplet oscillations in a planar Ge hole double quantum dot. Landau-Zener sweeps at different magnetic field directions allow us to disentangle the effects of the spin-orbit induced spin-flip term from those caused by strongly site-dependent and anisotropic quantum dot g tensors. Our work, therefore, provides new insights into the hole spin-orbit interaction, necessary for optimizing future qubit experiments.

Quantum-enabled operation of a microwave-optical interface - Sahu, Rishabh; Hease, William J; Rueda Sanchez, Alfredo R; Arnold, Georg M; Qiu, Liu; Fink, Johannes M (Nature Communications)
Solid-state microwave systems offer strong interactions for fast quantum logic and sensing but photons at telecom wavelength are the ideal choice for high-density low-loss quantum interconnects. A general-purpose interface that can make use of single photon effects requires < 1 input noise quanta, which has remained elusive due to either low efficiency or pump induced heating. Here we demonstrate coherent electro-optic modulation on nanosecond-timescales with only 0.16+0.02−0.01 microwave input noise photons with a total bidirectional transduction efficiency of 8.7% (or up to 15% with 0.41+0.02−0.02), as required for near-term heralded quantum network protocols. The use of short and high-power optical pump pulses also enables near-unity cooperativity of the electro-optic interaction leading to an internal pure conversion efficiency of up to 99.5%. Together with the low mode occupancy this provides evidence for electro-optic laser cooling and vacuum amplification as predicted a decade ago.

PaReBrick: PArallel REarrangements and BReaks identification toolkit - Zabelkin, Alexey; Yakovleva, Yulia; Bochkareva, Olga; Alexeev, Nikita (Bioinformatics)
Motivation High plasticity of bacterial genomes is provided by numerous mechanisms including horizontal gene transfer and recombination via numerous flanking repeats. Genome rearrangements such as inversions, deletions, insertions and duplications may independently occur in different strains, providing parallel adaptation or phenotypic diversity. Specifically, such rearrangements might be responsible for virulence, antibiotic resistance and antigenic variation. However, identification of such events requires laborious manual inspection and verification of phyletic pattern consistency. Results Here, we define the term ‘parallel rearrangements’ as events that occur independently in phylogenetically distant bacterial strains and present a formalization of the problem of parallel rearrangements calling. We implement an algorithmic solution for the identification of parallel rearrangements in bacterial populations as a tool PaReBrick. The tool takes a collection of strains represented as a sequence of oriented synteny blocks and a phylogenetic tree as input data. It identifies rearrangements, tests them for consistency with a tree, and sorts the events by their parallelism score. The tool provides diagrams of the neighbors for each block of interest, allowing the detection of horizontally transferred blocks or their extra copies and the inversions in which copied blocks are involved. We demonstrated PaReBrick’s efficiency and accuracy and showed its potential to detect genome rearrangements responsible for pathogenicity and adaptation in bacterial genomes.

Worst-case rigidity analysis and optimization for assemblies with mechanical joints - Liu, Zhenyuan; Hu, Jingyu; Xu, Hao; Song, Peng; Zhang, Ran; Bickel, Bernd; Fu, Chi-Wing (Computer Graphics Forum)
We study structural rigidity for assemblies with mechanical joints. Existing methods identify whether an assembly is structurally rigid by assuming parts are perfectly rigid. Yet, an assembly identified as rigid may not be that “rigid” in practice, and existing methods cannot quantify how rigid an assembly is. We address this limitation by developing a new measure, worst-case rigidity, to quantify the rigidity of an assembly as the largest possible deformation that the assembly undergoes for arbitrary external loads of fixed magnitude. Computing worst-case rigidity is non-trivial due to non-rigid parts and different joint types. We thus formulate a new computational approach by encoding parts and their connections into a stiffness matrix, in which parts are modeled as deformable objects and joints as soft constraints. Based on this, we formulate worst-case rigidity analysis as an optimization that seeks the worst-case deformation of an assembly for arbitrary external loads, and solve the optimization problem via an eigenanalysis. Furthermore, we present methods to optimize the geometry and topology of various assemblies to enhance their rigidity, as guided by our rigidity measure. In the end, we validate our method on a variety of assembly structures with physical experiments and demonstrate its effectiveness by designing and fabricating several structurally rigid assemblies.

Very short mountings are enough for sperm transfer in Littorina saxatilis - Perini, Samuel; Butlin, Rogerk; Westram, Anja M; Johannesson, Kerstin (Journal of Molluscan Studies)
Conflict over reproduction between females and males exists because of anisogamy and promiscuity. Together they generate differences in fitness optima between the sexes and result in antagonistic coevolution of female and male reproductive traits. Mounting duration is likely to be a compromise between male and female interests whose outcome depends on the intensity of sexual selection. The timing of sperm transfer during mounting is critical. For example, mountings may be interrupted before sperm is transferred as a consequence of female or male choice, or they may be prolonged to function as mate guarding. In the highly promiscuous intertidal snail Littorina saxatilis, mountings vary substantially in duration, from less than a minute to more than an hour, and it has been assumed that mountings of a few minutes do not result in any sperm being transferred. Here, we examined the timing of sperm transfer, a reproductive trait that is likely affected by sexual conflict. We performed time-controlled mounting trials using L. saxatilis males and virgin females, aiming to examine indirectly when the transfer of sperm starts. We observed the relationship between mounting duration and the proportion of developing embryos out of all eggs and embryos in the brood pouch. Developing embryos were observed in similar proportions in all treatments (i.e. 1, 5 and 10 or more minutes at which mountings were artificially interrupted), suggesting that sperm transfer begins rapidly (within 1 min) in L. saxatilis and very short matings do not result in sperm shortage in the females. We discuss how the observed pattern can be influenced by predation risk, population density, and female status and receptivity.

Exploring high-resolution cryo-ET and subtomogram averaging capabilities of contemporary DEDs - Obr, Martin; Hagen, Wim J.H.; Dick, Robert A.; Yu, Lingbo; Kotecha, Abhay; Schur, Florian KM (Journal of Structural Biology)
The potential of energy filtering and direct electron detection for cryo-electron microscopy (cryo-EM) has been well documented. Here, we assess the performance of recently introduced hardware for cryo-electron tomography (cryo-ET) and subtomogram averaging (STA), an increasingly popular structural determination method for complex 3D specimens. We acquired cryo-ET datasets of EIAV virus-like particles (VLPs) on two contemporary cryo-EM systems equipped with different energy filters and direct electron detectors (DED), specifically a Krios G4, equipped with a cold field emission gun (CFEG), Thermo Fisher Scientific Selectris X energy filter, and a Falcon 4 DED; and a Krios G3i, with a Schottky field emission gun (XFEG), a Gatan Bioquantum energy filter, and a K3 DED. We performed constrained cross-correlation-based STA on equally sized datasets acquired on the respective systems. The resulting EIAV CA hexamer reconstructions show that both systems perform comparably in the 4–6 Å resolution range based on Fourier-Shell correlation (FSC). In addition, by employing a recently introduced multiparticle refinement approach, we obtained a reconstruction of the EIAV CA hexamer at 2.9 Å. Our results demonstrate the potential of the new generation of energy filters and DEDs for STA, and the effects of using different processing pipelines on their STA outcomes.
Keywords: Structural Biology

Developmentally regulated impairment of parvalbumin interneuron synaptic transmission in an experimental model of Dravet syndrome - Kaneko, Keisuke; Currin, Christopher; Goff, Kevin M.; Wengert, Eric R.; Somarowthu, Ala; Vogels, Tim P; Goldberg, Ethan M. (Cell Reports)
Dravet syndrome is a neurodevelopmental disorder characterized by epilepsy, intellectual disability, and sudden death due to pathogenic variants in SCN1A with loss of function of the sodium channel subunit Nav1.1. Nav1.1-expressing parvalbumin GABAergic interneurons (PV-INs) from young Scn1a+/− mice show impaired action potential generation. An approach assessing PV-IN function in the same mice at two time points shows impaired spike generation in all Scn1a+/− mice at postnatal days (P) 16–21, whether deceased prior or surviving to P35, with normalization by P35 in surviving mice. However, PV-IN synaptic transmission is dysfunctional in young Scn1a+/− mice that did not survive and in Scn1a+/− mice ≥ P35. Modeling confirms that PV-IN axonal propagation is more sensitive to decreased sodium conductance than spike generation. These results demonstrate dynamic dysfunction in Dravet syndrome: combined abnormalities of PV-IN spike generation and propagation drives early disease severity, while ongoing dysfunction of synaptic transmission contributes to chronic pathology.

Structure of respiratory complex I – An emerging blueprint for the mechanism - Kampjut, Domen; Sazanov, Leonid A (Current Opinion in Structural Biology)
Complex I is one of the major respiratory complexes, conserved from bacteria to mammals. It oxidises NADH, reduces quinone and pumps protons across the membrane, thus playing a central role in the oxidative energy metabolism. In this review we discuss our current state of understanding the structure of complex I from various species of mammals, plants, fungi, and bacteria, as well as of several complex I-related proteins. By comparing the structural evidence from these systems in different redox states and data from mutagenesis and molecular simulations, we formulate the mechanisms of electron transfer and proton pumping and explain how they are conformationally and electrostatically coupled. Finally, we discuss the structural basis of the deactivation phenomenon in mammalian complex I.
Keywords: Molecular Biology; Structural Biology

Magnetic field resilience of three-dimensional transmons with thin-film Al/AlOx/Al Josephson junctions approaching 1 T - Krause, J.; Dickel, C.; Vaal, E.; Vielmetter, M.; Feng, J.; Bounds, R.; Catelani, G.; Fink, Johannes M; Ando, Yoichi (Physical Review Applied)
Magnetic-field-resilient superconducting circuits enable sensing applications and hybrid quantum computing architectures involving spin or topological qubits and electromechanical elements, as well as studying flux noise and quasiparticle loss. We investigate the effect of in-plane magnetic fields up to 1 T on the spectrum and coherence times of thin-film three-dimensional aluminum transmons. Using a copper cavity, unaffected by strong magnetic fields, we can probe solely the effect of magnetic fields on the transmons. We present data on a single-junction and a superconducting-quantum-interference-device (SQUID) transmon that are cooled down in the same cavity. As expected, the transmon frequencies decrease with increasing field, due to suppression of the superconducting gap and a geometric Fraunhofer-like contribution. Nevertheless, the thin-film transmons show strong magnetic field resilience: both transmons display microsecond coherence up to at least 0.65 T, and T1 remains above 1μs over the entire measurable range. SQUID spectroscopy is feasible up to 1 T, the limit of our magnet. We conclude that thin-film aluminum Josephson junctions are suitable hardware for superconducting circuits in the high-magnetic-field regime.

Enhanced thermoelectric performance in SnTe due to the energy filtering effect introduced by Bi2O3 - Hong, Tao; Guo, Changrong; Wang, Dongyang; Qin, Bingchao; Chang, Cheng; Gao, Xiang; Zhao, Li Dong (Materials Today Energy)
SnTe is a promising Pb-free thermoelectric (TE) material with high electrical conductivity. We discovered the synergistic effect of Bi2O3 on enhancing the average power factor (PF) and overall ZT value of the SnTe-based thermoelectric material. The introduction of Bi2O3 forms plenty of SnO2, Bi2O3, and Bi-rich nanoprecipitates. These interfaces between the SnTe matrix and the nanoprecipitates can enhance the average PF through the energy filtering effect. On the other hand, abundant and diverse nanoprecipitates can significantly diminish the lattice thermal conductivity (κlat) through enhanced phonon scattering. The synergistic effect of Bi2O3 resulted in a maximum ZT (ZTmax) value of 0.9 at SnTe-2% Bi2O3 and an average ZT (ZTave) value of 0.4 for SnTe-4% Bi2O3 from 300 K to 823 K. The work provides an excellent reference to develop non-toxic high-performance TE materials.

On the operator norm of a Hermitian random matrix with correlated entries - Reker, Jana (Random Matrices: Theory and Applications)
We consider a correlated NxN Hermitian random matrix with a polynomially decaying metric correlation structure. By calculating the trace of the moments of the matrix and using the summable decay of the cumulants, we show that its operator norm is stochastically dominated by one.
Keywords: Discrete Mathematics and Combinatorics; Statistics; Probability and Uncertainty; Statistics and Probability; Algebra and Number Theory